Ultrahigh-molecular-weight polyethylene powder and molded product

By employing ultra-high molecular weight polyethylene powder with defined properties and controlled production methods, the challenges of moldability and uniformity in molded products are addressed, resulting in high-quality articles with enhanced mechanical properties.

JP2025013222APending Publication Date: 2025-01-24ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024106221
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-07-11
Filing Date
2024-07-01
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Ultra-high molecular weight polyethylene powder exhibits low fluidity and poor moldability due to changes in shape, surface condition, and pore condition during heating, leading to issues like air bubbles and distortion in molded products, and existing solutions do not adequately address uniformity and quality of molded articles.

Method used

The use of ultra-high molecular weight polyethylene powder with specific intrinsic viscosity, particle size, dissolution time, and pore characteristics, along with controlled production methods, to enhance moldability and produce high-quality molded products.

Benefits of technology

The specified ultra-high molecular weight polyethylene powder enables the production of uniform gels and high-quality molded articles with improved mechanical properties and reduced processing time, such as secondary battery separators and high-strength fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025013222000009
    Figure 2025013222000009
  • Figure 2025013222000010
    Figure 2025013222000010
  • Figure 2025013222000001
    Figure 2025013222000001
Patent Text Reader

Abstract

To provide an ultrahigh-molecular-weight polyethylene powder or the like which greatly reduces the kneading time, allows the rapid production of a uniform gel, and enables the formation of gels with high polymer concentrations, while offering superior moldability.SOLUTION: An ultrahigh-molecular-weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 38.0 dL / g or less, an average particle size D50 of 50 μm or more and 400 μm or less, and a dissolution time of powder with a D50 particle size of 5 seconds or more and 80 seconds or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an ultra-high molecular weight polyethylene powder and a molded article. [Background technology]

[0002] Polyethylene is used in a wide variety of applications, such as films, sheets, microporous membranes, fibers, foams, and pipes. Polyethylene is used because it is easy to melt process, and the molded products obtained have high mechanical strength and excellent chemical resistance, rigidity, etc. Among them, ultra-high molecular weight polyethylene has a large molecular weight, and therefore has high mechanical strength, excellent sliding properties and abrasion resistance, as well as excellent chemical stability and long-term reliability.

[0003] However, ultra-high molecular weight polyethylene has low fluidity even when melted at a temperature equal to or higher than its melting point. Therefore, various methods are used, such as a compression molding method in which polyethylene powder is compressed and molded under heating and then cut, or a molding method in which the polyethylene is dissolved in a solvent such as liquid paraffin, stretched, and then the solvent is removed to form the polyethylene into a sheet or thread shape.

[0004] Ultra-high molecular weight polyethylene is molded in powder form, but compared to pellets, the powder has a larger surface area and contains fine pores.

[0005] Regarding the pore state of the polyethylene powder, for example, Patent Document 1 discloses a polyethylene powder that can be quickly dissolved in a solvent and can give a molded product with little undissolved matter by adjusting the specific surface area determined by the BET method and the pore volume determined by mercury intrusion porosimetry to appropriate ranges.

[0006] Furthermore, for example, Patent Document 2 discloses a polyethylene powder that can obtain a molded product with little undissolved matter by adjusting the ratio of the median diameter and mode diameter of pores measured by mercury intrusion porosimetry to an appropriate range.

[0007] In recent years, polyethylene powders have been proposed which are excellent in moldability and allow high-quality molded articles to be obtained.

[0008] For example, Patent Document 3 discloses a polyethylene powder that has excellent solubility and can improve the productivity and product quality in processing (particularly wet extrusion) by simultaneously imparting a predetermined particle size distribution and a predetermined swelling ratio to the polyethylene powder.

[0009] Furthermore, for example, Patent Document 4 discloses a polyethylene polymer powder in which the intrinsic viscosity IV and the contents of Al, Mg and Si are controlled within specific ranges, thereby improving oxidation resistance and effectively improving the uniformity and smoothness of a thin film.

[0010] Furthermore, for example, Patent Document 5 discloses an ethylene-based polymer which, by containing a nonmagnetic substance satisfying specific conditions, reduces entanglement of the ethylene-based polymer when processed and stretched, and when made into a high-strength fiber, has excellent low-temperature tensile strength, and when made into a microporous film, has excellent film shrinkage rate and low-temperature puncture strength.

[0011] Furthermore, for example, Patent Document 6 discloses that a molded product having excellent processability and dimensional accuracy can be obtained by adjusting the difference between the swelling start temperature and the dissolution start temperature of ultra-high molecular weight polyethylene powder and by adjusting the impregnation rate of liquid paraffin into the ultra-high molecular weight polyethylene powder.

[0012] For example, Patent Document 7 describes a particle size of D 10 , D 50 and D. 90 It is disclosed that by controlling the swelling onset temperature of the ultra-high molecular weight polyethylene powder within a specific range, it is possible to obtain an ultra-high molecular weight polyethylene powder that is excellent in moldability when previously swollen at a low temperature, and a high-quality molded product obtained by molding the same. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] JP 2017-088773 A [Patent Document 2] JP 2017-145306 A [Patent Document 3] JP 2019-019265 A [Patent Document 4] JP 2019-070117 A [Patent Document 5] JP 2019-123777 A [Patent Document 6] WO2021 / 193544 publication [Patent Document 7] WO2023-054514 publication Summary of the Invention [Problem to be solved by the invention]

[0014] As described above, ultra-high molecular weight polyethylene powder has a large surface area compared to pellets and has fine pores in the powder. Therefore, the shape, surface condition, crystal state, pore state, etc. of the powder change during heating, so when molding the ultra-high molecular weight polyethylene powder, it is required to adjust the temperature to an appropriate level and perform processing such as dissolution and compression. When compression molding the ultra-high molecular weight polyethylene powder, if the preheating temperature before compression is not appropriate, air bubbles tend to remain in the molded body, or distortion tends to remain in the molded body and cause deformation after cooling.

[0015] The polyethylene powder described in Patent Document 1 has only adjusted powder properties such as specific surface area and pore volume, and the powder properties change significantly at the temperature at which it actually melts or dissolves, leaving room for improvement in terms of moldability.

[0016] In addition, the polyethylene powder described in Patent Document 2 also only specifies the pore size of the powder, and the pore size changes significantly during the heating process, so there is room for improvement in moldability, and it may be difficult to obtain a uniform molded product.

[0017] On the other hand, while the polyethylene powders described in Patent Documents 3 to 5 have relatively excellent moldability, obtaining a uniform gel in a short period of time has not been considered, and there is room for improvement in moldability and quality of molded articles.

[0018] Furthermore, the dissolution time (the time from the start of dissolution to the end of dissolution) of the polyethylene powders described in Patent Documents 6 and 7 in liquid paraffin has not been examined, and there is room for improvement in terms of molding processability and the quality of molded articles.

[0019] The present invention has been made in consideration of the above circumstances, and has an object to provide an ultra-high molecular weight polyethylene powder with excellent moldability that can significantly shorten the kneading time when using the ultra-high molecular weight polyethylene powder to produce a molded body, and can produce a uniform gel in a short time and a gel with a high polymer concentration, as well as a high-quality molded body obtained by molding the same (for example, a separator for secondary batteries that is excellent in terms of film thickness unevenness and puncture strength, and a fiber that is excellent in terms of yarn diameter unevenness and high-speed winding properties). [Means for solving the problem]

[0020] As a result of intensive research into solving the above problems, the inventors discovered that the above problems could be solved by using an ultra-high molecular weight polyethylene powder that dissolves in liquid paraffin within a specified period of time, and thus completed the present invention.

[0021] That is, the present invention is as follows. [1] The intrinsic viscosity IV is 1.0 dL / g or more and 38.0 dL / g or less, The average particle size D50 is 50 μm or more and 400 μm or less, The dissolution time of a powder with a particle size of D50 is 5 seconds or more and 80 seconds or less. Ultra-high molecular weight polyethylene powder. [2] The ultra-high molecular weight polyethylene powder according to [1], wherein the intrinsic viscosity IV is 13.5 dL / g or more and 38.0 dL / g or less. [3] The ultra-high molecular weight polyethylene powder according to [1] or [2], wherein the dissolution time is from 5 seconds to 40 seconds. [4] The ultra-high molecular weight polyethylene powder according to any one of [1] to [3], wherein the proportion of open pores in the powder having a particle diameter D50 is 3% or more and 70% or less. [5] The ultra-high molecular weight polyethylene powder according to any one of [1] to [4], wherein the surface thickness of a powder having a particle diameter D50 is 3 μm or more and 60 μm or less. [6] The ultra-high molecular weight polyethylene powder according to any one of [1] to [5], wherein the powder having a particle diameter D50 has an open pore diameter of 3 μm or more and 30 μm or less. [7] The ultra-high molecular weight polyethylene powder according to any one of [1] to [6], having a titanium content of 5 ppm or less. [8] The ultra-high molecular weight polyethylene powder according to any one of [1] to [7], having an aluminum content of 5 ppm or less. [9] A molded product of the ultra-high molecular weight polyethylene powder according to any one of [1] to [8].

[10] The molded article according to [9], which is a separator for a secondary battery.

[11] The molded article according to [9], wherein the molded article is a fiber.

[12] a slurry process of mixing the ultra-high molecular weight polyethylene powder with a first liquid paraffin and stirring the mixture at a temperature equal to or lower than the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry; a gelling step of mixing the slurry with a second liquid paraffin having a temperature of 150° C. or more and 300° C. or less to obtain a gel for raw yarn having a temperature of 140° C. or more and 200° C. or less; an extrusion step of extruding the gel to obtain a raw yarn; an extraction step of extracting the first liquid paraffin and the second liquid paraffin from the raw yarn to obtain a raw yarn for drawing; a yarn drawing step of heating and drawing the yarn to be drawn; having The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 13.5 dL / g or more and 38.0 dL / g or less, The ultra-high molecular weight polyethylene powder has an average particle size D50 of 50 μm or more and 400 μm or less, The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds or more and 80 seconds or less. A method for producing high strength fibers.

[13] The method for producing a high-strength fiber according to

[12] , further comprising a kneading step of kneading the yarn gel prior to the extrusion step.

[14] a slurry process of mixing the ultra-high molecular weight polyethylene powder with a first liquid paraffin and stirring the mixture at a temperature equal to or lower than the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry; A gelling step of mixing the slurry with a second liquid paraffin having a temperature of 150° C. or more and 300° C. or less to obtain a gel for pressing having a temperature of 140° C. or more and 200° C. or less; a pressing step of hot pressing the gel for pressing to obtain a gel sheet; A film stretching step of stretching the gel sheet to obtain a stretched film; an extraction step of extracting the first liquid paraffin and the second liquid paraffin from the stretched membrane; having The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 13.0 dL / g or less, The ultra-high molecular weight polyethylene powder has an average particle size D50 of 50 μm or more and 400 μm or less, The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds or more and 80 seconds or less. A method for producing a microporous membrane.

[15] The method for producing a microporous membrane according to

[14] , further comprising a kneading step of kneading the press gel prior to the pressing step.

[16] In the slurry step, the stirring temperature is 25° C. or more and 120° C. or less, The method for producing a high-strength fiber according to

[12] or

[13] , wherein in the gelling step, the polyethylene concentration of the yarn gel is 3% by mass or more and 20% by mass or less.

[17] In the kneading step, The temperature is 140°C or more and 200°C or less, The duration is between 5 and 180 minutes, The method for producing a high-strength fiber according to

[13] or

[16] , wherein the rotation speed is 3 rpm or more and 50 rpm or less.

[18] A quenching step is performed after the extrusion step, The time from the extrusion step to the quenching step is 0 s or more and 10 s or less, The method for producing a high-strength fiber according to any one of

[12] ,

[13] ,

[16] and

[17] , wherein the temperature in the quenching step is 5°C or higher and 30°C or lower.

[19] An extrusion preparation step is provided prior to the extrusion step, The temperature of the extrusion preparation step is 140° C. or more and 200° C. or less, The method for producing a high-strength fiber according to any one of

[12] ,

[13] and

[16] to

[18] , wherein the extrusion preparation step lasts for 5 minutes or more and 90 minutes or less.

[20] In the extrusion step, The extrusion speed is 5 mm / min or more and 20 mm / min or less, The winding speed is 200 mm / min or more and 1600 mm / min or less, The discharge rate is 0.2 g / min or more and 1.5 g / min or less, The method for producing a high-strength fiber according to any one of

[12] ,

[13] and

[16] to

[19] , wherein the spinning hole diameter is 0.8 mm or more and 1.5 mm or less. [twenty one] In the extraction step, an extraction solvent is used, The extraction solvent is hexane or dichloromethane; The method for producing a high-strength fiber according to any one of

[12] ,

[13] and

[16] to

[20] , wherein the extraction time is from 3 hours to 24 hours. [twenty two] The method for producing a high strength fiber according to any one of

[12] ,

[13] and

[16] to

[21] , wherein the raw yarn drawing step involves multi-stage drawing. [twenty three] The method for producing a high-strength fiber according to

[22] , wherein the multi-stage drawing is a two-stage drawing. [twenty four] The two-stage drawing includes a first drawing process and a second drawing process, In the first stretching step, The delivery speed is 50 mm / min or more and 200 mm / min or less, The winding speed is 1000 mm / min or more and 4000 mm / min or less, The temperature is 110°C or higher and 155°C or lower, In the second stretching step, The delivery speed is 50 mm / min or more and 200 mm / min or less, The winding speed is 100 mm / min or more and 500 mm / min or less, The method for producing a high-strength fiber according to

[23] , wherein the temperature is 130°C or higher and 155°C or lower. [twenty five] In the slurry step, the stirring temperature is 25° C. or more and 120° C. or less, The method for producing a microporous membrane according to

[14] or

[15] , wherein in the gelling step, the pressing gel has a polyethylene concentration of 20% by mass or more and 55% by mass or less.

[26] In the kneading step, The temperature is 140°C or more and 250°C or less, The duration is between 5 and 60 minutes, The method for producing a microporous membrane according to

[15] or

[25] , wherein the rotation speed is 30 rpm or more and 100 rpm or less.

[27] In the pressing step, A 1.0 mm metal frame was used so that the thickness of the gel sheet was 1.0 mm. Furthermore, temperature and pressure are adjusted in multiple stages, In the first stage, the temperature is between 180℃ and 220℃, the pressure is 1MPa, and the time is 3 minutes. In the second stage, the temperature is between 180℃ and 220℃, the pressure is 10MPa, and the time is 2 minutes. The method for producing a microporous membrane according to any one of

[14] ,

[15] ,

[25] and

[26] , wherein in the third stage, cooling is performed under conditions of a temperature of 20°C to 35°C, a pressure of 10 MPa, and a time of 5 minutes.

[28] In the film stretching step, The stretching is simultaneous biaxial stretching, The method for producing a microporous membrane according to any one of

[14] ,

[15] , and

[25] to

[27] , wherein the membrane is stretched at a temperature of 110°C to 130°C, and at a size of 5 to 20 times in the longitudinal direction and 5 to 20 times in the transverse direction.

[29] In the extraction step, an extraction solvent is used, The extraction solvent is hexane or dichloromethane; The method for producing a microporous membrane according to any one of

[14] ,

[15] , and

[25] to

[28] , wherein the extraction time is from 3 hours to 24 hours. Effect of the Invention

[0022] According to the present invention, it is possible to provide an ultra-high molecular weight polyethylene powder having excellent moldability, and a high-quality molded article obtained by molding the same. [Brief description of the drawings]

[0023] [Figure 1] The image shows a powder (particle) with a particle diameter of D50. The area surrounded by the dotted line on the outer periphery of the particle is called the "outer diameter of the particle." The diameter of the largest circle (shown by the dotted line) that fits into the interconnected pores is called the "interconnected pore diameter." The diameter of the largest circle (shown by the dotted line) that fits into the resin region is called the "wall thickness." [Diagram 2] The tomographic image of a powder with a particle size of D50 is shown. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Hereinafter, an embodiment of the present invention (hereinafter, also referred to as "the present embodiment") will be described in detail. Note that the present invention is not limited to the present embodiment, and can be modified in various ways without departing from the gist of the present invention.

[0025] [Ultra-high molecular weight polyethylene powder] The ultra-high molecular weight polyethylene powder of this embodiment (hereinafter simply referred to as "powder" or "polymer") has an intrinsic viscosity IV of 1.0 dL / g or more and 38.0 dL / g or less, preferably 1.5 dL / g or more and 33.0 dL / g or less, and more preferably 2.4 dL / g or more and 31.0 dL / g or less. The ultra-high molecular weight polyethylene powder of this embodiment has an intrinsic viscosity IV of not less than the above lower limit, thereby further improving the strength, and has an intrinsic viscosity IV of not more than the above upper limit, thereby further improving the molding processability.

[0026] Furthermore, the ultra-high molecular weight polyethylene powder of the present embodiment is not particularly limited, but for example, when used in a molded body for a separator for a secondary battery, the intrinsic viscosity IV is preferably 1.0 dL / g or more and 13.0 dL / g or less, more preferably 1.5 dL / g or more and 11.5 dL / g or less, and even more preferably 2.4 dL / g or more and 9.5 dL / g or less. A separator for a secondary battery obtained by molding an ultra-high molecular weight polyethylene powder having an intrinsic viscosity IV within the above range tends to be excellent in film strength, heat shrinkability, etc.

[0027] Furthermore, the ultra-high molecular weight polyethylene powder of the present embodiment is not particularly limited, but for example, when used for a fiber molding, the intrinsic viscosity IV is preferably 13.5 dL / g or more and 38.0 dL / g or less, more preferably 15.0 dL / g or more and 33.0 dL / g or less, and even more preferably 16.5 dL / g or more and 31.0 dL / g or less. Fibers obtained by molding (for example, general molding or molding when kneaded for a short time) ultra-high molecular weight polyethylene powder having an intrinsic viscosity IV within the above range tend to be excellent in thread strength, etc.

[0028] The method of controlling the intrinsic viscosity IV within the above range is not particularly limited, but for example, the polymerization temperature of the reactor when homopolymerizing ethylene or copolymerizing ethylene with olefins other than ethylene that can be copolymerized with ethylene can be changed. The intrinsic viscosity IV tends to be lower as the polymerization temperature is increased, and tends to be higher as the polymerization temperature is decreased. In addition, another method of controlling the intrinsic viscosity IV within the above range is not particularly limited, but for example, the type of organometallic compound used as a cocatalyst when homopolymerizing ethylene or copolymerizing ethylene with olefins other than ethylene that can be copolymerized with ethylene can be changed. In addition, another method of controlling the intrinsic viscosity IV within the above range is not particularly limited, but for example, the type of chain transfer agent added when homopolymerizing ethylene or copolymerizing ethylene with olefins other than ethylene that can be copolymerized with ethylene can be added. By adding a chain transfer agent, the intrinsic viscosity IV of the ultra-high molecular weight polyethylene produced at the same polymerization temperature tends to be lower. In the present embodiment, the intrinsic viscosity IV is not particularly limited, but can be determined, for example, by the method described in the Examples below.

[0029] The ultra-high molecular weight polyethylene powder of the present embodiment is preferably a powder made of an ethylene homopolymer and / or a copolymer of ethylene and an olefin other than ethylene that is copolymerizable with ethylene (hereinafter also referred to as a "comonomer") (hereinafter also referred to as an "ethylene-based polymer").

[0030] The comonomer copolymerizable with ethylene is not particularly limited, but specifically includes, for example, α-olefins having 3 to 15 carbon atoms, cyclic olefins having 3 to 15 carbon atoms, and copolymers represented by the formula CH2=CHR 1 (where R 1 is an aryl group having 6 to 12 carbon atoms.) and at least one comonomer selected from the group consisting of linear, branched or cyclic dienes having 3 to 15 carbon atoms. Among these, α-olefins having 3 to 15 carbon atoms are preferred.

[0031] The α-olefin is not particularly limited, but examples thereof include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, and 1-tetradecene.

[0032] The ultra-high molecular weight polyethylene powder according to the present embodiment may be one made from ethylene produced from, for example, biomass-derived naphtha or biomass-derived ethanol. For example, the biomass-derived ultra-high molecular weight polyethylene powder can be produced by a cracking method using biomass-derived naphtha as a raw material.

[0033] The average particle diameter (D50) of the ultra-high molecular weight polyethylene powder of this embodiment is 50 μm or more and 400 μm or less, preferably 70 μm or more and 300 μm or less, more preferably 90 μm or more and 250 μm or less, even more preferably 100 μm or more and 200 μm or less, and most preferably 120 μm or more and 180 μm or less. By making the average particle size (D50) 50 μm or more, clogging in the extruder hopper due to reduced fluidity can be suppressed, improving productivity. Also, by making the average particle size (D50) 400 μm or less, a sufficient amount of liquid paraffin can be allowed to penetrate into the powder, making it possible to produce a uniform gel with disentangled particles. In other words, it is possible to suppress the non-uniformity of the gel due to insufficient penetration of liquid paraffin.

[0034] The method for controlling the average particle size (D50) within the above range is not particularly limited, but for example, there is a method of appropriately adjusting the conditions in the polymerization system (polymerization temperature, ethylene pressure, etc.). Specifically, there is a method of increasing the polymerization temperature and / or polymerization pressure.

[0035] The method for measuring the average particle size (D50) of the ultra-high molecular weight polyethylene powder is not particularly limited, but can be carried out, for example, by the method described in the Examples below.

[0036] [Dissolving time of ultra-high molecular weight polyethylene powder] The dissolution time of the ultra-high molecular weight polyethylene powder of this embodiment is 5 seconds or more and 80 seconds or less, preferably 5 seconds or more and 70 seconds or less, more preferably 5 seconds or more and 60 seconds or less, even more preferably 5 seconds or more and 40 seconds or less, and most preferably 5 seconds or more and 35 seconds or less. The dissolution time is calculated according to the following methods 1 and 2. [Method 1; How to measure D50] The particle size of the target ultra-high molecular weight polyethylene powder is measured using a laser particle size distribution analyzer with methanol as the dispersion medium, and a cumulative particle size distribution from the small particle size side is created based on the measurement, and the particle size at the cumulative 50% is defined as D50. [Method 2: Dissolution time measurement method] The dissolution time of a powder with a particle diameter of D50 is obtained. First, one ultra-high molecular weight polyethylene powder whose major axis diameter and minor axis diameter (the shortest distance between parallel lines in the plane diagram of the particle observed using an optical microscope is the minor axis diameter of the particle, and the longest distance between parallel lines perpendicular to the shortest distance is the major axis diameter of the particle) are randomly collected while checking with an optical microscope. One collected ultra-high molecular weight polyethylene powder particle (hereinafter also referred to as "measurement particle") is set on a slide glass, 0.05 mL of liquid paraffin is dripped onto the measurement particle using a 1 mL syringe, and then a cover glass is placed on the measurement particle to sandwich the measurement particle. Then, the slide glass is set on a heat stage and the temperature is raised from room temperature to 150°C under the following heating conditions. The appearance of the measurement particle during heating is photographed every 5 seconds with an optical microscope equipped with a camera. The circle equivalent diameter of the measurement particle is calculated from each obtained observation image, and the time from the state where the circle equivalent diameter is largest to the disappearance of the powder is taken as the dissolution time. This procedure was repeated 10 times, and the maximum and minimum values ​​were excluded to calculate the average value of the remaining 8 values, from which the final dissolution time was calculated. (Temperature rise conditions) Heating rate from room temperature to 35℃: 5℃ / min Heating rate in the range of 35℃~80℃: 8℃ / min Heating rate in the range of 80℃~150℃: 5℃ / min

[0037] The ultra-high molecular weight polyethylene powder of the present embodiment has a dissolution time within the above range, and therefore, for example, when fibers (e.g., high-strength fibers) or secondary battery separators (e.g., microporous membranes) are wet extruded, the energy required for the wet extrusion process can be reduced, thereby reducing the environmental load and significantly improving the production efficiency of molded articles. Generally, wet extrusion refers to a process in which a powder is impregnated with liquid paraffin, the slurry is kneaded in an extruder while being heated, and the gel-like material is processed into various molded products. Here, the amount of entanglement of molecular chains in the gel determines the processability of the molded product. Ultra-high molecular weight polyethylene powder has a high amount of entanglement of molecular chains in the amorphous part, and it is difficult to obtain a uniform gel in which the entanglements are disentangled. In other words, even if the wet extrusion processing conditions (temperature, time, screw rotation speed) are adjusted, it is difficult to obtain a uniform gel in which the molecular chains are disentangled, and it is important to reduce the amount of entanglement in the amorphous part of the powder itself. Here, the dissolution behavior of polyethylene powder will be explained. When polyethylene powder is impregnated with liquid paraffin, the liquid paraffin penetrates (dissolves) into the polyethylene powder, causing the polyethylene powder to swell. Since liquid paraffin cannot easily penetrate into the crystalline parts of the polyethylene powder, it is believed to penetrate into the amorphous parts, and it has actually been confirmed that the long crystal period of the polyethylene powder extends as it swells. In other words, swelling is believed to be a phenomenon in which liquid paraffin penetrates between the lamellar crystals of the polyethylene powder and pushes open the amorphous parts. If the molecular chains in the amorphous portion are highly entangled at this time, swelling is inhibited and the amount of liquid paraffin that penetrates into the powder is reduced, resulting in poor solubility of the powder (long dissolution time = more than 80 seconds), and a uniform gel in which the chains are disentangled cannot be obtained even with long-term kneading. On the other hand, if the amount of entanglement of the molecular chains in the amorphous part is small, the amount of liquid paraffin that penetrates into the powder is also large, so the solubility of the powder is improved (short dissolution time = 5 seconds to 80 seconds), and a uniform gel in which the entanglements are disentangled can be obtained by kneading for a short time. As a result, when wet extrusion processing is performed, a high-quality molded product, for example, a separator for a secondary battery with suppressed thickness variation and high breaking strength, or a fiber with suppressed yarn diameter unevenness and capable of being stretched at high speed can be obtained. However, if the amount of entanglement of the molecular chains in the amorphous part is too small (too short dissolution time = less than 5 seconds), it is not possible to suppress the thermal shrinkage of the molded product after wet extrusion processing, which is thought to lead to a decrease in strength. This is thought to be because the moderate amount of entanglement remains, which can suppress the shrinkage of the extended chains, and as a result, the thermal shrinkage is alleviated. From the above, it is important to set the amount of entanglement of molecular chains in the amorphous portion within an appropriate range, since being too much or too little is bad. To this end, it is necessary to control the dissolution time of the powder to between 5 seconds and 80 seconds.

[0038] The method for controlling the dissolution time of the ultra-high molecular weight polyethylene powder within the above range is not particularly limited, and examples thereof include a method in which the powder is immersed in liquid paraffin and vacuum degassed while being heated (hereinafter also referred to as control method 1), and a method in which liquid paraffin is added to a polymerization solvent during prepolymerization, the polymer obtained by polymerization is polymerized, and the polymer is used as a prepolymerization catalyst for main polymerization (hereinafter also referred to as control method 2).

[0039] The mechanism by which the dissolution time of the ultra-high molecular weight polyethylene powder can be controlled within the above range by the above-mentioned method is not clear, and the present inventors presume, but are not limited to, as follows.

[0040] The reason for the above control method 1 is unclear and is not limited to the following, but it is important to immerse the powder in liquid paraffin, apply a temperature (50°C to 100°C) at which the powder does not melt and the molecular chains can move, and leave it under vacuum (300 Pa to 400 Pa) for 1 hour to 6 hours, allowing the liquid paraffin to fully penetrate into the powder pores and gradually untangling the molecular chains over time. Next, immerse the powder in hexane for 5 hours to 24 hours to extract the liquid paraffin from the powder, and dry it at 25°C to 50°C for 24 hours, which is thought to be able to obtain a powder with a short dissolution time (5 seconds to 80 seconds).

[0041] The reason for the above control method 2 is unclear and is not limited to the following, but it is believed that a powder with a short dissolution time (5 seconds to 80 seconds) can be obtained by adding 55 to 70 mass% liquid paraffin to the polymerization solvent during prepolymerization, polymerizing the polymer obtained by using the polymer as a prepolymerization catalyst, and then removing the liquid paraffin from the powder after polymerization is completed. It is believed that the liquid paraffin added to the polymerization solvent is adjusted to a temperature equivalent to the polymerization temperature, and the liquid paraffin has the effect of suppressing entanglement of molecular chains during the molecular chain growth reaction process.

[0042] [Percentage of open pores in ultra-high molecular weight polyethylene powder] The proportion of interconnected pores in the ultra-high molecular weight polyethylene powder of this embodiment is, for example, 3% or more and 70% or less, preferably 5% or more and 70% or less, more preferably 7% or more and 70% or less, even more preferably 10% or more and 50% or less, and most preferably 15% or more and 40% or less. By making the ratio of interconnected pores 3% or more, the liquid paraffin can penetrate sufficiently into the powder, making it possible to produce a uniform gel with a short kneading time. Also, by making the ratio of interconnected pores 70% or less, it is possible to suppress a decrease in the filling rate in the packaging bag due to the high porosity structure of the powder, and to avoid high production costs. The proportion of communicating pores is calculated according to the method described in the Examples below.

[0043] [Surface thickness of ultra-high molecular weight polyethylene powder] The surface thickness of the ultra-high molecular weight polyethylene powder of this embodiment is, for example, 3 μm or more and 60 μm or less, preferably 5 μm or more and 50 μm or less, more preferably 5 μm or more and 40 μm or less, even more preferably 5 μm or more and 35 μm or less, and most preferably 5 μm or more and 30 μm or less. By making the surface thickness 3 μm or more, it is possible to prevent the powder particles from fusing together due to the melting of the powder surface, and to produce a homogeneous gel with disentangled particles.In addition, by making the surface thickness 60 μm or less, it is possible to allow the liquid paraffin to penetrate into the powder in a short time, and to produce a homogeneous gel with disentangled particles. The surface thickness is calculated according to the method described in the Examples section below.

[0044] [Open hole diameter of ultra-high molecular weight polyethylene powder] The diameter of the continuous pores of the ultra-high molecular weight polyethylene powder of this embodiment is, for example, 3 μm or more and 30 μm or less, preferably 4 μm or more and 30 μm or less, more preferably 6 μm or more and 30 μm or less, even more preferably 8 μm or more and 30 μm or less, and most preferably 10 μm or more and 30 μm or less. By making the interconnected pore diameter 30 μm or less, liquid paraffin can penetrate into the powder by capillary action, making it possible to produce a uniform gel with disentangled particles.By making the interconnected pore diameter 3 μm or more, a sufficient amount of liquid paraffin can penetrate into the powder, making it possible to produce a uniform gel with disentangled particles. The diameter of the communicating holes is calculated according to the method described in the Examples below.

[0045] The method for controlling the proportion of interconnected pores, surface thickness, and interconnected pore diameter of the ultra-high molecular weight polyethylene powder within the above-mentioned ranges is not particularly limited, and examples thereof include a method in which a polymer obtained by prepolymerization is used as a prepolymerization catalyst to polymerize under high pressure conditions (hereinafter, also referred to as control method 3).

[0046] The mechanism by which the above-mentioned method enables the proportion of interconnected pores, surface thickness, and interconnected pore diameter of the ultra-high molecular weight polyethylene powder to be controlled within the above-mentioned ranges is not clear and, although not limited to, the inventors presume it as follows.

[0047] The reason for the above control method 3 is unclear and is not limited to the following, but by using a prepolymerization catalyst (low-temperature (5°C to 20°C), short-time (0.5 to 2 hours) polymerization, ethylene charge amount 5 NL to 20 NL) and polymerizing under high-pressure (0.5 MPa to 1.0 MPa) conditions, the polymerization can be performed in a state where the initial polymerization activity is highly active. Therefore, it is considered that a large amount of polymerization heat energy is generated in the polymerization process, and in the process of this heat energy escaping from the center of the powder to the outside, continuous pores extending from the center of the powder to the surface are formed, and the diameter of the continuous pores can be controlled by further adjusting the amount of this heat energy.

[0048] [Titanium (Ti) and aluminum (Al) content in ultra-high molecular weight polyethylene powder] The titanium (Ti) and aluminum (Al) contents in the ultra-high molecular weight polyethylene powder of this embodiment are, for example, 5 ppm or less, preferably 4 ppm or less, and more preferably 3 ppm or less. In general, a large amount of metal derived from catalyst residue remaining in the ultra-high molecular weight polyethylene powder tends to cause uneven thickness of the molded body, but the ultra-high molecular weight polyethylene powder of this embodiment tends to have excellent quality by adjusting the titanium (Ti) and aluminum (Al) contents to 5 ppm or less. In addition, safety tends to be improved when used for battery applications.

[0049] The titanium (Ti) and aluminum (Al) contents in the ultra-high molecular weight polyethylene powder can be controlled by the productivity of the ethylene homopolymer or ethylene-based polymer per unit catalyst. The productivity of the ethylene homopolymer or ethylene-based polymer can be controlled by the polymerization temperature, polymerization pressure, and slurry concentration of the reactor during production. That is, the productivity of the ethylene homopolymer or ethylene-based polymer used in this embodiment can be increased, but is not particularly limited, by, for example, increasing the polymerization temperature, increasing the polymerization pressure, and / or increasing the slurry concentration. As other methods, the productivity can be controlled by selecting the type of promoter component, decreasing the concentration of the promoter component, or washing the ethylene homopolymer or ethylene-based polymer with an acid or alkali when polymerizing the ethylene homopolymer or ethylene-based polymer.

[0050] The method for measuring the titanium (Ti) and aluminum (Al) contents is not particularly limited, but can be carried out, for example, by the method described in the examples below.

[0051] [Method of manufacturing ultra-high molecular weight polyethylene powder] The method for producing the ultra-high molecular weight polyethylene powder of this embodiment will be described in detail below.

[0052] (Catalyst Component) The catalyst component used in the production of the ultra-high molecular weight polyethylene powder according to the present embodiment is not particularly limited, but examples thereof include general Ziegler-Natta catalysts and metallocene catalysts. <Ziegler-Natta catalyst> The Ziegler-Natta catalyst is preferably a catalyst comprising a solid catalyst component [A] and an organometallic compound component [B], in which the solid catalyst component [A] is an olefin polymerization catalyst produced by reacting an organomagnesium compound (A-1) represented by the following formula 1, which is soluble in an inert hydrocarbon solvent, with a titanium compound (A-2) represented by the following formula 2. (A-1):(M 1 )α(Mg)β(R 2 )a (R 3 ) b (Y 1 ) c ...Formula 1 (In the formula, M 1 is a metal atom belonging to the group consisting of groups 12, 13, and 14 of the periodic table, and R 2 and R 3 is a hydrocarbon group having 2 to 20 carbon atoms, and Y 1 is alkoxy, siloxy, aryloxy, amino, amido, -N=CR 4 , R 5 , -SR 6 (where R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 may be different from each other.) or a β-keto acid residue, and α, β, a, b, and c are real numbers that satisfy the following relationships: 0≦α, 0<β, 0≦a, 0≦b, 0≦c, 0 <a+b、0≦c / (α+β)≦2、nα+2β=a+b+c(ここで、nはM 1 Represents the valence of .

[0053] (A-2): Ti(OR 7 ) d X 1 (4-d) ...Formula 2 (In formula 2, d is a real number between 0 and 4, and R 7 is a hydrocarbon group having 1 to 20 carbon atoms, and X 1 is a halogen atom.)

[0054] The inert hydrocarbon solvent used in the reaction of (A-1) and (A-2) is not particularly limited, but specific examples include aliphatic hydrocarbons such as pentane, hexane, and heptane; aromatic hydrocarbons such as benzene and toluene; and alicyclic hydrocarbons such as cyclohexane and methylcyclohexane.

[0055] First, (A-1) will be described. (A-1) is shown in the form of an organomagnesium complex compound soluble in an inert hydrocarbon solvent, and includes all dihydrocarbylmagnesium compounds and complexes of these compounds with other metal compounds. The relational formula nα+2β=a+b+c of the symbols α, β, a, b, and c indicates the stoichiometry of the valence of the metal atom and the substituent.

[0056] In formula 1, R 2 and R 3 The hydrocarbon group having 2 to 20 carbon atoms is not particularly limited, but specific examples thereof include an alkyl group, a cycloalkyl group, and an aryl group, such as ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, and phenyl groups. Among these, an alkyl group is preferred. When α>0, the metal atom M 1 As the metal atom, a metal atom belonging to the group consisting of Groups 12, 13, and 14 of the periodic table can be used, and although there is no particular limitation, examples thereof include zinc, boron, aluminum, etc. Among these, aluminum and zinc are preferred.

[0057] metal atom M 1 The ratio β / α of magnesium to R is not particularly limited, but is preferably 0.1 to 30, and more preferably 0.5 to 10. When a certain organomagnesium compound with α=0 is used, it is not particularly limited, but for example, 2 In the case where R is 1-methylpropyl or the like, it is soluble in an inert hydrocarbon solvent, and such a compound also gives a preferable result in this embodiment. 2 , R 3 It is recommended that patients meet one of the following three groups: (1), (2), or (3).

[0058] Group(1):R 2 , R 3 At least one of R is a secondary or tertiary alkyl group having 4 to 6 carbon atoms. 2 , R 3are both alkyl groups having 4 to 6 carbon atoms, and at least one of them is a secondary or tertiary alkyl group. Group(2):R 2 and R 3 and R are alkyl groups having different numbers of carbon atoms. 2 is an alkyl group having 2 or 3 carbon atoms, and R 3 is an alkyl group having 4 or more carbon atoms. Group(3):R 2 , R 3 At least one of R is a hydrocarbon group having 6 or more carbon atoms. 2 , R 3 The alkyl group must have 12 or more carbon atoms when added together.

[0059] Specific examples of these groups are shown below. In group (1), the secondary or tertiary alkyl group having 4 to 6 carbon atoms is not particularly limited, but specific examples include 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 2-methylbutyl, 2-ethylpropyl, 2,2-dimethylpropyl, 2-methylpentyl, 2-ethylbutyl, 2,2-dimethylbutyl, and 2-methyl-2-ethylpropyl groups. Among these, the 1-methylpropyl group is particularly preferred.

[0060] In addition, the alkyl group having 2 or 3 carbon atoms in group (2) is not particularly limited, but specific examples thereof include ethyl, 1-methylethyl, and propyl groups. Among these, the ethyl group is particularly preferred. In addition, the alkyl group having 4 or more carbon atoms is not particularly limited, but specific examples thereof include butyl, pentyl, hexyl, heptyl, and octyl groups. Among these, the butyl and hexyl groups are particularly preferred.

[0061] Furthermore, in group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, but specific examples include hexyl, heptyl, octyl, nonyl, decyl, phenyl, 2-naphthyl groups, etc. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and octyl groups are particularly preferred.

[0062] Generally, the more carbon atoms contained in the alkyl group, the more easily the compound dissolves in an inert hydrocarbon solvent, and the more the viscosity of the solution tends to increase. Therefore, it is preferable to use an alkyl group with a moderately long chain in terms of handling. The above-mentioned organomagnesium compound can be used after diluting with an inert hydrocarbon solvent, but it can be used without any problem even if a small amount of Lewis basic compound such as ether, ester, or amine is contained or remains in the solution.

[0063] Next, Y 1 In formula 1, Y 1 is alkoxy, siloxy, aryloxy, amino, amido, -N=CR 4 ,R 5 , -SR 6 (where R 4 , R 5 and R 6 each independently represents a hydrocarbon group having 2 to 20 carbon atoms, or a β-keto acid residue.

[0064] In formula 1, R 4 , R 5 and R 6The hydrocarbon group represented by the formula (I) is preferably an alkyl group or aryl group having 1 to 12 carbon atoms, particularly preferably an alkyl group or aryl group having 3 to 10 carbon atoms. Although not particularly limited, examples thereof include methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl groups, etc. Among these, butyl, 1-methylpropyl, 2-methylpentyl, and 2-ethylhexyl groups are particularly preferred.

[0065] In addition, in formula 1, Y 1 is preferably an alkoxy group or a siloxy group. The alkoxy group is not particularly limited, but specifically, for example, methoxy, ethoxy, propoxy, 1-methylethoxy, butoxy, 1-methylpropoxy, 1,1-dimethylethoxy, pentoxy, hexoxy, 2-methylpentoxy, 2-ethylbutoxy, 2-ethylpentoxy, 2-ethylhexoxy, 2-ethyl-4-methylpentoxy, 2-propylheptoxy, 2-ethyl-5-methyloctoxy, octoxy, phenoxy, and naphthoxy groups are preferred. Among these, butoxy, 1-methylpropoxy, 2-methylpentoxy, and 2-ethylhexoxy groups are more preferred. The siloxy group is not particularly limited, but specifically, for example, hydrodimethylsiloxy, ethylhydromethylsiloxy, diethylhydrosiloxy, trimethylsiloxy, ethyldimethylsiloxy, diethylmethylsiloxy, and triethylsiloxy groups are preferred. Of these, hydrodimethylsiloxy, ethylhydromethylsiloxy, diethylhydrosiloxy and trimethylsiloxy groups are more preferred.

[0066] In this embodiment, the synthesis method of (A-1) is not particularly limited. For example, 2 MgX 1 , and formula R 2 Mg(R 2has the meaning mentioned above, and X 1 is a halogen.) and an organomagnesium compound of the formula M 1 R 3 n and M 1 R 3 (n-1) H(M 1 , and R 3 has the meaning as above, and n is M 1 ) in an inert hydrocarbon solvent at 25° C. to 150° C., and then, if necessary, reacting the compound with an organometallic compound of the formula Y 1 -H(Y 1 has the above-mentioned meaning.) or Y 1 Among these, the compound can be synthesized by reacting an organomagnesium compound and / or an organoaluminum compound having a functional group represented by the formula Y 1 When reacting a compound represented by formula Y with a compound represented by formula -H, the order of the reactions is not particularly limited. 1 -H, a method of adding a compound represented by the formula Y 1 Either a method of adding the organomagnesium compound to the compound represented by --H or a method of adding both simultaneously can be used.

[0067] In this embodiment, Y relative to all metal atoms in (A-1) 1 The molar composition ratio c / (α+β) of is 0≦c / (α+β)≦2, and preferably 0≦c / (α+β)<1. 1 When the molar composition ratio of is 2 or less, the reactivity of (A-1) with respect to (A-2) tends to be improved.

[0068] Next, (A-2) will be described. (A-2) is a titanium compound represented by formula 2. (A-2): Ti(OR 7 ) d X 1 (4-d) ...Formula 2 (In formula 2, d is a real number between 0 and 4, and R 7 is a hydrocarbon group having 1 to 20 carbon atoms, and X 1 is a halogen atom.)

[0069] In the above formula 2, d is preferably 0 or more and 1 or less, and more preferably 0. 7 The hydrocarbon group represented by the formula (I) is not particularly limited, but specific examples thereof include aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl groups; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl groups; and aromatic hydrocarbon groups such as phenyl and naphthyl groups. Among these, aliphatic hydrocarbon groups are preferred. X 1 The halogen represented by the formula (I) may be, for example, chlorine, bromine, or iodine. Among these, chlorine is preferred. In this embodiment, (A-2) is particularly preferably titanium tetrachloride. In this embodiment, it is possible to use a mixture of two or more of the compounds selected from the above.

[0070] Next, the reaction between (A-1) and (A-2) will be described. The reaction is preferably carried out in an inert hydrocarbon solvent, more preferably in an aliphatic hydrocarbon solvent such as hexane or heptane. The molar ratio of (A-1) to (A-2) in the reaction is not particularly limited, but the molar ratio (Ti / Mg) of Ti atoms contained in (A-2) to Mg atoms contained in (A-1) is preferably 0.1 to 10, more preferably 0.3 to 3. The reaction temperature is not particularly limited, but is preferably carried out in the range of -80°C to 150°C, more preferably -40°C to 100°C. The order of addition of (A-1) and (A-2) is not particularly limited, and any of the following methods is possible: adding (A-2) after (A-1), adding (A-2) after (A-1), or adding (A-1) and (A-2) simultaneously, but the method of adding (A-1) and (A-2) simultaneously is preferred. In this embodiment, the solid catalyst component [A] obtained by the above reaction is used as a slurry solution using an inert hydrocarbon solvent.

[0071] Another example of the Ziegler-Natta catalyst component used in this embodiment is preferably an olefin polymerization catalyst comprising a solid catalyst component [C] and an organometallic compound component [B], the solid catalyst component [C] being produced by supporting an organomagnesium compound (C-4) represented by formula 5 and a titanium compound (C-5) represented by formula 6, which are soluble in an inert hydrocarbon solvent, on a support (C-3) prepared by reacting an organomagnesium compound (C-1) represented by formula 3 and soluble in an inert hydrocarbon solvent with a chlorinating agent (C-2) represented by formula 4.

[0072] (C-1):(M 2 )γ(Mg)δ(R 8 ) e (R 9 ) f (OR 10 ) g ...Formula 3 (In formula 3, M 2 is a metal atom belonging to the group consisting of groups 12, 13, and 14 of the periodic table, and R 8 , R9 and R 10 are hydrocarbon groups having 2 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers that satisfy the following relationships: 0≦γ, 0<δ, 0≦e, 0≦f, 0≦g, 0 <e+f、0≦g / (γ+δ)≦2、kγ+2δ=e+f+g(ここで、kはM 2 Represents the valence of .

[0073] (C-2):H h SiCl i R 11 (4-(h+i)) ...Formula 4 (In formula 4, R 11 is a hydrocarbon group having 1 to 12 carbon atoms, and h and i are real numbers that satisfy the following relationship: 0 <h、0<i、0<h+i≦4)

[0074] (C-4):(M 1 )α(Mg)β(R 2 ) a (R 3 ) b Y 1 c ...Formula 5 (In formula 5, M 1 is a metal atom belonging to the group consisting of groups 12, 13, and 14 of the periodic table, and R 2 and R 3 is a hydrocarbon group having 2 to 20 carbon atoms, and Y 1 is alkoxy, siloxy, aryloxy, amino, amido, -N=CR 4 ,R 5 , -SR 6 (where R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 may be different from each other.) or a β-keto acid residue, and α, β, a, b, and c are real numbers that satisfy the following relationships: 0≦α, 0<β, 0≦a, 0≦b, 0≦c, 0 <a+b、0≦c / (α+β)≦2、nα+2β=a+b+c(ここで、nはM 1 Represents the valence of .

[0075] (C-5): Ti(OR 7 ) d X 1 (4-d) ...Formula 6 (In formula 6, d is a real number between 0 and 4, and R 7 is a hydrocarbon group having 1 to 20 carbon atoms, and X 1 is a halogen atom.)

[0076] First, (C-1) will be explained. (C-1) is shown as a form of an organomagnesium complex compound soluble in an inert hydrocarbon solvent, but it includes all dihydrocarbylmagnesium compounds and complexes of this compound with other metal compounds. The relational formula kγ+2δ=e+f+g of the symbols γ, δ, e, f, and g in formula 3 indicates the stoichiometry of the valence of the metal atom and the substituent.

[0077] In the above formula 3, R 8 Or R 9 The hydrocarbon group represented by is not particularly limited, but specifically, it is an alkyl group, a cycloalkyl group, or an aryl group, and examples thereof include methyl, ethyl, propyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, and phenyl groups. Among these, R 8 and R 9 are alkyl groups. When α>0, the metal atom M 2 As the metal atom, a metal atom belonging to the group consisting of Groups 12, 13, and 14 of the periodic table can be used, and although there is no particular limitation, examples thereof include zinc, boron, aluminum, etc. Among these, aluminum and zinc are particularly preferred.

[0078] metal atom M 2 The ratio δ / γ of magnesium to R is not particularly limited, but is preferably 0.1 to 30, more preferably 0.5 to 10. When a certain organomagnesium compound with γ=0 is used, for example, R 8 In the case where R is 1-methylpropyl or the like, it is soluble in an inert hydrocarbon solvent, and such a compound also gives a preferable result in this embodiment.8 , R 9 It is recommended that patients be in one of the following three groups: (1), (2), or (3).

[0079] Group(1):R 8 , R 9 At least one of R is a secondary or tertiary alkyl group having 4 to 6 carbon atoms. 8 , R 9 Both have 4 to 6 carbon atoms, and at least one of them is a secondary or tertiary alkyl group. Group(2):R 8 and R 9 and R are alkyl groups having different carbon numbers. 8 is an alkyl group having 2 or 3 carbon atoms, and R 9 is an alkyl group having 4 or more carbon atoms. Group(3):R 8 , R 9 At least one of R is a hydrocarbon group having 6 or more carbon atoms. 8 , R 9 The sum of the carbon atoms contained in the alkyl group is 12 or more.

[0080] Specific examples of these groups are shown below. In group (1), specific examples of the secondary or tertiary alkyl group having 4 to 6 carbon atoms include 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 2-methylbutyl, 2-ethylpropyl, 2,2-dimethylpropyl, 2-methylpentyl, 2-ethylbutyl, 2,2-dimethylbutyl, and 2-methyl-2-ethylpropyl groups. Among these, the 1-methylpropyl group is particularly preferred.

[0081] In addition, in group (2), the alkyl group having 2 or 3 carbon atoms is not particularly limited, but examples thereof include ethyl, 1-methylethyl, and propyl groups. Among these, the ethyl group is particularly preferred. In addition, the alkyl group having 4 or more carbon atoms is not particularly limited, but specific examples thereof include butyl, pentyl, hexyl, heptyl, and octyl groups. Among these, the butyl and hexyl groups are particularly preferred.

[0082] Furthermore, in group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, but specific examples include hexyl, heptyl, octyl, nonyl, decyl, phenyl, 2-naphthyl groups, etc. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and octyl groups are particularly preferred.

[0083] Generally, the more carbon atoms contained in the alkyl group, the more easily the compound dissolves in an inert hydrocarbon solvent, and the more the viscosity of the solution tends to increase. Therefore, it is preferable to use an alkyl group with a moderate chain length in terms of handling. The above-mentioned organomagnesium compound is used as an inert hydrocarbon solution, but it can be used without any problem even if a small amount of Lewis basic compound such as ether, ester, or amine is contained or remains in the solution.

[0084] Next, the alkoxy group (OR 10 ) will be explained. 10 The hydrocarbon group represented by the formula (I) is preferably an alkyl group or aryl group having 1 to 12 carbon atoms, particularly preferably an alkyl group or aryl group having 3 to 10 carbon atoms. 10is not particularly limited, specific examples thereof include methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl groups, etc. Among these, butyl, 1-methylpropyl, 2-methylpentyl and 2-ethylhexyl groups are particularly preferred.

[0085] In this embodiment, the synthesis method of (C-1) is not particularly limited, but it is preferable to use a compound represented by the formula R 8 MgX 1 and formula R 8 Mg(R 8 has the meaning mentioned above, and X 1 is a halogen atom.) and an organomagnesium compound of the formula M 2 R 9 k and formula M 2 R 9 (k-1) H(M 2 , R 9 and k has the same meaning as above) in an inert hydrocarbon solvent at a temperature of 25° C. to 150° C., and if necessary, subsequently reacting with R 9 (R 9 has the above meaning.) R soluble in alcohol or inert hydrocarbon solvent having a hydrocarbon group represented by 9 In another preferred method, the compound is reacted with an alkoxy magnesium compound having a hydrocarbon group represented by the following formula: and / or an alkoxy aluminum compound.

[0086] Among these, when an organomagnesium compound soluble in an inert hydrocarbon solvent is reacted with an alcohol, the order of the reaction is not particularly limited, and any of the following methods can be used: adding the alcohol to the organomagnesium compound, adding the organomagnesium compound to the alcohol, or adding both at the same time. In this embodiment, the reaction ratio of the organomagnesium compound soluble in an inert hydrocarbon solvent and the alcohol is not particularly limited, but the molar composition ratio g / (γ+δ) of the alkoxy group to the total metal atom in the alkoxy group-containing organomagnesium compound obtained as a result of the reaction is 0≦g / (γ+δ)≦2, and preferably 0≦g / (γ+δ)<1.

[0087] Next, (C-2) will be described. (C-2) is a silicon chloride compound represented by formula 4 and having at least one Si—H bond.

[0088] (C-2):H h SiCl i R 11 (4-(h+i)) ...Formula 4 (In formula 4, R 11 is a hydrocarbon group having 1 to 12 carbon atoms, and h and i are real numbers that satisfy the following relationship: 0 <h、0<i、0<h+i≦4)

[0089] In Equation 4, R 11 The hydrocarbon group represented by is not particularly limited, but specifically includes an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, and an aromatic hydrocarbon group, such as methyl, ethyl, propyl, 1-methylethyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, and phenyl groups. Among these, alkyl groups having 1 to 10 carbon atoms are preferred, and alkyl groups having 1 to 3 carbon atoms, such as methyl, ethyl, propyl, and 1-methylethyl groups, are more preferred. Furthermore, h and i are numbers greater than 0 that satisfy the relationship h+i≦4, and it is preferred that i is 2 to 3.

[0090] These compounds are not particularly limited, but specific examples include HSiCl3, HSiCl2CH3, HSiCl2C2H5, HSiCl2(C3H7), HSiCl2(2-C3H7), HSiCl2(C4H9), HSiCl2(C6H5), HSiCl2(4-Cl-C6H4), HSiCl2(CH=CH2), HSiCl2(CH2C6H5), HSiCl2(1-C 10 H7), HSiCl2(CH2CH=CH2), H2SiCl(CH3), H2SiCl(C2H5), HSiCl(CH3)2, HSiCl(C2H5)2, HSiCl(CH3)(2-C3H7), HSiCl(CH3)(C6H5), HSiCl(C6H5)2, etc. Silicon chloride compounds consisting of these compounds or mixtures of two or more selected from these compounds are used. Among these, HSiCl3, HSiCl2CH3, HSiCl(CH3)2, and HSiCl2(C3H7) are preferred, and HSiCl3 and HSiCl2CH3 are more preferred.

[0091] Next, the reaction between (C-1) and (C-2) will be described. In the reaction, it is preferable to dilute (C-2) in advance with an inert hydrocarbon solvent, chlorinated hydrocarbon such as 1,2-dichloroethane, o-dichlorobenzene, dichloromethane, etc.; ether medium such as diethyl ether, tetrahydrofuran, etc.; or a mixture of these. Among these, inert hydrocarbon solvents are more preferable in terms of catalyst performance. The reaction ratio between (C-1) and (C-2) is not particularly limited, but the silicon atom contained in (C-2) is preferably 0.01 mol or more and 100 mol or less, more preferably 0.1 mol or more and 10 mol or less, per 1 mol of magnesium atom contained in (C-1).

[0092] There is no particular restriction on the reaction method between (C-1) and (C-2), and any of the following methods can be used: simultaneous addition method in which (C-1) and (C-2) are simultaneously introduced into a reactor and reacted; method in which (C-2) is charged in advance into a reactor and then (C-1) is introduced into the reactor; or method in which (C-1) is charged in advance into a reactor and then (C-2) is introduced into the reactor. Among these, the method in which (C-2) is charged in advance into a reactor and then (C-1) is introduced into the reactor is preferred. The support (C-3) obtained by the above reaction is preferably separated by filtration or decantation, and then thoroughly washed with an inert hydrocarbon solvent to remove unreacted materials or by-products.

[0093] The reaction temperature between (C-1) and (C-2) is not particularly limited, but is preferably 25°C to 150°C, more preferably 30°C to 120°C, and even more preferably 40°C to 100°C. In the simultaneous addition method in which (C-1) and (C-2) are simultaneously introduced into a reactor and reacted, it is preferable to adjust the temperature of the reactor to a predetermined temperature in advance, and adjust the temperature in the reactor to a predetermined temperature while performing the simultaneous addition, thereby adjusting the reaction temperature to a predetermined temperature. In the method in which (C-2) is charged in a reactor in advance and then (C-1) is introduced into the reactor, it is preferable to adjust the temperature of the reactor in which the silicon chloride compound is charged to a predetermined temperature, and adjust the temperature in the reactor to a predetermined temperature while introducing the organomagnesium compound into the reactor, thereby adjusting the reaction temperature to a predetermined temperature. In the method of charging (C-1) into a reactor in advance and then introducing (C-2) into the reactor, it is preferable to adjust the temperature of the reactor into which (C-1) has been charged to a predetermined temperature, and then adjust the temperature inside the reactor to a predetermined temperature while introducing (C-2) into the reactor, thereby adjusting the reaction temperature to a predetermined temperature.

[0094] Next, the organomagnesium compound (C-4) will be described. As (C-4), the compound represented by the above formula 5 (C-4) is preferable. (C-4):(M 1 )α(Mg)β(R 2 ) a (R3 ) b Y 1 c ...Formula 5 (In formula 5, M 1 is a metal atom belonging to the group consisting of groups 12, 13, and 14 of the periodic table, and R 2 and R 3 is a hydrocarbon group having 2 to 20 carbon atoms, and Y 1 is alkoxy, siloxy, aryloxy, amino, amido, -N=CR 4 ,R 5 , -SR 6 (where R 4 , R 5 and R 6 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 may be different from each other.) or a β-keto acid residue, and α, β, a, b, and c are real numbers that satisfy the following relationships: 0≦α, 0<β, 0≦a, 0≦b, 0 <a+b、0≦c / (α+β)≦2、nα+2β=a+b+c(ここで、nはM 1 Represents the valence of .

[0095] The amount of (C-4) used is preferably 0.1 or more and 10 or less, more preferably 0.5 or more and 5 or less, in terms of the molar ratio of magnesium atoms contained in (C-4) to titanium atoms contained in (C-5).

[0096] The temperature for the reaction of (C-4) and (C-5) is not particularly limited, but is preferably in the range of -80°C or higher and 150°C or lower, and more preferably in the range of -40°C or higher and 100°C or lower.

[0097] The concentration of (C-4) when used is not particularly limited, but is preferably 0.1 mol / L or more and 2 mol / L or less, and more preferably 0.5 mol / L or more and 1.5 mol / L or less, based on the titanium atoms contained in (C-4). It is preferable to use an inert hydrocarbon solvent to dilute (C-4).

[0098] There is no particular restriction on the order of addition of (C-4) and (C-5) to (C-3), and any of the following methods is possible: adding (C-4) followed by (C-5), adding (C-4) followed by (C-5), or adding (C-4) and (C-5) simultaneously. Among these, the method of adding (C-4) and (C-5) simultaneously is preferred. The reaction between (C-4) and (C-5) is carried out in an inert hydrocarbon solvent, and it is preferable to use an aliphatic hydrocarbon solvent such as hexane or heptane. The catalyst thus obtained is used as a slurry solution using an inert hydrocarbon solvent.

[0099] Next, (C-5) will be described. In this embodiment, (C-5) is a titanium compound represented by the above formula 6.

[0100] (C-5): Ti(OR 7 ) d X 1 (4-d) ...Formula 6 (In formula 6, d is a real number between 0 and 4, and R 7 is a hydrocarbon group having 1 to 20 carbon atoms, and X 1 is a halogen atom.)

[0101] In Equation 6, R 7 The hydrocarbon group represented by the formula (I) is not particularly limited, but specific examples thereof include aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl groups; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl groups; and aromatic hydrocarbon groups such as phenyl and naphthyl groups. Among these, aliphatic hydrocarbon groups are preferred. X 1 The halogen represented by is not particularly limited, but specifically includes, for example, chlorine, bromine, and iodine. Among these, chlorine is preferable. The (C-5) selected from the above may be used alone or in combination of two or more.

[0102] The amount of (C-5) used is not particularly limited, but is preferably 0.01 or more and 20 or less, particularly preferably 0.05 or more and 10 or less, in terms of the molar ratio to the magnesium atoms contained in the carrier (C-3).

[0103] The reaction temperature of (C-5) is not particularly limited, but is preferably in the range of -80°C or higher and 150°C or lower, and more preferably in the range of -40°C or higher and 100°C or lower. In this embodiment, the method for supporting (C-5) on (C-3) is not particularly limited. A method of reacting an excess of (C-5) with (C-3) or a method of efficiently supporting (C-5) by using a third component may be used, but a method of supporting (C-5) by reacting (C-5) with an organomagnesium compound (C-4) is preferred.

[0104] Next, the organometallic compound component [B] used in this embodiment will be described. The solid catalyst component used in this embodiment becomes a highly active polymerization catalyst by combining with the organometallic compound component [B]. The organometallic compound component [B] is sometimes called a "co-catalyst." The organometallic compound component [B] is preferably a compound containing a metal belonging to the group consisting of Groups 1, 2, 12, and 13 of the periodic table, and is particularly preferably an organoaluminum compound and / or an organomagnesium compound.

[0105] As the organoaluminum compound, it is preferable to use a compound represented by the following formula 7 alone or in combination.

[0106] AlR 12 j Z 1 (3-j) ...Formula 7 (In formula 7, R 12 is a hydrocarbon group having 1 to 20 carbon atoms, Z 1 is a radical belonging to the group consisting of hydrogen, halogen, alkoxy, aryloxy, and siloxy groups, and j is a number between 2 and 3.

[0107] In the above formula 7, R 12The hydrocarbon group having 1 to 20 carbon atoms represented by the formula (1) is not particularly limited, but specifically includes aliphatic hydrocarbons, aromatic hydrocarbons, and alicyclic hydrocarbons, and for example, trialkylaluminum such as trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, tri(2-methylpropyl)aluminum (or triisobutylaluminum), tripentylaluminum, tri(3-methylbutyl)aluminum, trihexylaluminum, trioctylaluminum, and tridecylaluminum, halogenated aluminum compounds such as diethylaluminum chloride, ethylaluminum dichloride, bis(2-methylpropyl)aluminum chloride, ethylaluminum sesquichloride, and diethylaluminum bromide, alkoxyaluminum compounds such as diethylaluminum ethoxide and bis(2-methylpropyl)aluminum butoxide, siloxyaluminum compounds such as dimethylhydrosiloxyaluminum dimethyl, ethylmethylhydrosiloxyaluminum diethyl, and ethyldimethylsiloxyaluminum diethyl, and mixtures thereof are preferred. Among these, trialkylaluminum compounds are particularly preferred.

[0108] As the organomagnesium compound, an organomagnesium compound which is soluble in an inert hydrocarbon solvent and is represented by the above formula 3 is preferred.

[0109] (M 2 )γ(Mg)δ(R 8 ) e (R 9 ) f (OR 10 ) g ...Formula 3 (In formula 3, M 2 is a metal atom belonging to the group consisting of groups 12, 13, and 14 of the periodic table, and R 8 , R 9 and R 10are hydrocarbon groups having 2 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers that satisfy the following relationships: 0≦γ, 0<δ, 0≦e, 0≦f, 0≦g, 0 <e+f、0≦g / (γ+δ)≦2、kγ+2δ=e+f+g(ここで、kはM 2 Represents the valence of .

[0110] The organomagnesium compound is shown in the form of an organomagnesium complex compound soluble in an inert hydrocarbon solvent, but includes all dialkylmagnesium compounds and complexes of this compound with other metal compounds. 2 , R 8 , R 9 , OR 10 As already mentioned, it is preferable that the organomagnesium compound has high solubility in an inert hydrocarbon solvent, so that δ / γ is preferably in the range of 0.5 to 10. 2 More preferred are compounds in which is aluminum. The combination ratio of the solid catalyst component and the organometallic compound component [B] is not particularly limited, but it is preferable that the organometallic compound component [B] is 1 mmol or more and 3,000 mmol or less per gram of the solid catalyst component.

[0111] <Metallocene catalyst> As an example of using a metallocene catalyst, a general transition metal compound is used. The method for producing the metallocene catalyst is not particularly limited, but for example, the method described in Japanese Patent No. 4868853 can be mentioned. Such a metallocene catalyst is composed of two catalyst components: (a) a transition metal compound having a cyclic η-bonding anion ligand, and (b) an activator capable of forming a complex that expresses catalytic activity by reacting with the transition metal compound.

[0112] The transition metal compound having a cyclic η-bonding anion ligand used in this embodiment can be represented, for example, by the following formula 8. L 1 j W k M 3 X 2p X 3 q ...Formula 8

[0113] In Equation 8, L 1 each independently represents an η-bonding cyclic anionic ligand selected from the group consisting of a cyclopentadienyl group, an indenyl group, a tetrahydroindenyl group, a fluorenyl group, a tetrahydrofluorenyl group, and an octahydrofluorenyl group, and the ligand optionally has 1 to 8 substituents, each independently being a substituent having up to 20 non-hydrogen atoms selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogen atom, a halogen-substituted hydrocarbon group having 1 to 12 carbon atoms, an aminohydrocarbyl group having 1 to 12 carbon atoms, a hydrocarbyloxy group having 1 to 12 carbon atoms, a dihydrocarbylamino group having 1 to 12 carbon atoms, a hydrocarbylphosphino group having 1 to 12 carbon atoms, a silyl group, an aminosilyl group, a hydrocarbyloxysilyl group having 1 to 12 carbon atoms, and a halosilyl group.

[0114] In Equation 8, M 3 is a transition metal selected from the group of transition metals belonging to Group 4 of the periodic table having a formal oxidation number of +2, +3 or +4, and has at least one ligand L 1 To 5 Represents a bound transition metal.

[0115] In formula 8, W is a divalent substituent having up to 50 non-hydrogen atoms, L 1 and M. 3 Each bond has a valence of 1, resulting in L 1 and M 3 represents a divalent substituent which cooperates with X to form a metallocycle; 2 are each independently a monovalent anionic σ-bonded ligand; M 3 and a divalent anionic σ-bonded ligand that is divalently bonded to L 1 and M. 3 and divalent anionic σ-bonded ligands each having a valence of 1 to 1 and each having a valence of 1, and each having up to 60 non-hydrogen atoms.

[0116] In Equation 8, X 2 each independently represents a neutral Lewis base coordinating compound having up to 40 non-hydrogen atoms; X 3 represents a neutral Lewis base coordinating compound.

[0117] j is 1 or 2, provided that when j is 2, two ligands L 1 are bonded to each other via a divalent group having up to 20 non-hydrogen atoms, and the divalent group is a group selected from the group consisting of hydrocarbadiyl groups having 1 to 20 carbon atoms, halohydrocarbadiyl groups having 1 to 12 carbon atoms, hydrocarbyleneoxy groups having 1 to 12 carbon atoms, hydrocarbyleneamino groups having 1 to 12 carbon atoms, silanediyl groups, halosilanediyl groups, and silyleneamino groups.

[0118] k is 0 or 1, p is 0, 1 or 2, provided that X 2 is a monovalent anionic σ-bonded ligand, or L 1 and M. 3 If p is a divalent anionic σ-bonded ligand bound to M 3 is an integer that is one or more smaller than the formal oxidation number of X 2 M 3 If the ligand is a divalent anionic σ-bonded ligand bound only to M, then p is M 3 is an integer that is (j+1) or more smaller than the formal oxidation number of

[0119] Ligand X in the compound of formula 8 2 Examples of the alkyl group include halides, hydrocarbon groups having 1 to 60 carbon atoms, hydrocarbyloxy groups having 1 to 60 carbon atoms, hydrocarbylamide groups having 1 to 60 carbon atoms, hydrocarbyl phosphide groups having 1 to 60 carbon atoms, hydrocarbyl sulfide groups having 1 to 60 carbon atoms, silyl groups, and composite groups thereof.

[0120] The neutral Lewis base coordinating compound X in the compound of formula 8 3Examples of the substituent include phosphines, ethers, amines, olefins having 2 to 40 carbon atoms, dienes having 1 to 40 carbon atoms, and divalent groups derived from these compounds.

[0121] In this embodiment, the transition metal compound having a cyclic η-bonding anion ligand is preferably a transition metal compound represented by the above formula 8 (where j is 1). A preferred example of the compound represented by the above formula 8 (where j is 1) is a compound represented by the following formula 9.

[0122] [ka]

[0123] In Equation 9, M 4 represents a transition metal selected from the group consisting of titanium, zirconium, nickel, and hafnium, the formal oxidation number of which is +2, +3, or +4; R 13 each independently represents a substituent having up to 20 non-hydrogen atoms selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 8 carbon atoms, a silyl group, a germyl group, a cyano group, a halogen atom, and a composite group thereof, provided that the substituent R 13 is a hydrocarbon group having 1 to 8 carbon atoms, a silyl group, or a germyl group, two adjacent substituents R 13 are bonded to each other to form a divalent group, whereby the two adjacent substituents R 13 can cooperate with the bonds between the two carbon atoms of the cyclopentadienyl ring to form a ring.

[0124] In Equation 9, X 4each independently represents a substituent having up to 20 non-hydrogen atoms selected from the group consisting of a halide, a hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbyloxy group having 1 to 18 carbon atoms, a hydrocarbylamino group having 1 to 18 carbon atoms, a silyl group, a hydrocarbylamide group having 1 to 18 carbon atoms, a hydrocarbyl phosphide group having 1 to 18 carbon atoms, a hydrocarbyl sulfide group having 1 to 18 carbon atoms, and composite groups thereof, provided that in some cases, two substituents X 4 can cooperate to form a neutral conjugated diene or divalent group having 4 to 30 carbon atoms.

[0125] In Equation 9, Y 2 -O-, -S-, -NR * -OR-PR * -, where R * represents a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, a hydrocarbyloxy group having 1 to 8 carbon atoms, a silyl group, a halogenated alkyl group having 1 to 8 carbon atoms, a halogenated aryl group having 6 to 20 carbon atoms, or a composite group thereof.

[0126] In formula 9, Z 2 is SiR * 2. CR * 2. SiR * 2SiR * 2. CR * 2CR *2 , C.R. * =CR * , C.R. * 2SiR * 2 or GeR * 2, where R * is as defined above and n is 1, 2 or 3.

[0127] Examples of the transition metal compound having a cyclic η-bonding anion ligand used in this embodiment include the following compounds. The zirconium-based compound is not particularly limited, but specifically includes, for example, bis(methylcyclopentadienyl)zirconium dimethyl, bis(n-butylcyclopentadienyl)zirconium dimethyl, bis(indenyl)zirconium dimethyl, bis(1,3-dimethylcyclopentadienyl)zirconium dimethyl, (pentamethylcyclopentadienyl)(cyclopentadienyl)zirconium dimethyl, bis(cyclopentadienyl)zirconium dimethyl, bis(pentamethylcyclopentadienyl)zirconium dimethyl, bis(fluorenyl)zirconium dimethyl, ethylenebis(indenyl)zirconium dimethyl, ethylenebis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, ethylenebis(4-methyl-1-indenyl)zirconium dimethyl, ethylenebis(5-methyl-1-indenyl)zirconium dimethyl, ) zirconium dimethyl, ethylene bis (6-methyl-1-indenyl) zirconium dimethyl, ethylene bis (7-methyl-1-indenyl) zirconium dimethyl, ethylene bis (5-methoxy-1-indenyl) zirconium dimethyl, ethylene bis (2,3-dimethyl-1-indenyl) zirconium dimethyl, ethylene bis (4,7-dimethyl-1-indenyl) zirconium dimethyl, ethylene bis (4,7-dimethoxy-1-indenyl) zirconium dimethyl, methylene bis (cyclopentadienyl) zirconium dimethyl, isopropylidene (cyclopentadienyl) zirconium dimethyl, isopropylidene (cyclopentadienyl-fluorenyl) zirconium dimethyl, silylene bis (cyclopentadienyl) zirconium dimethyl, dimethylsilylene (cyclopentadienyl) zirconium dimethyl, and the like.

[0128] The titanium-based compound is not particularly limited, but specifically includes, for example, [(Nt-butylamido)(tetramethyl-η 5 -cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(Nt-butylamido)(tetramethyl-η 5-Cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-methylamido)(tetramethyl-η 5 -Cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-phenylamido)(tetramethyl-η 5 -Cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-benzylamido)(tetramethyl-η 5 -Cyclopentadienyl)dimethylsilane]titanium dimethyl, [(Nt-butylamido)(η 5 -cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(Nt-butylamido)(η 5 -Cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-methylamido)(η 5 -cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(N-methylamido)(η 5 -Cyclopentadienyl)dimethylsilane]titanium dimethyl, [(Nt-butylamido)(η 5 -indenyl)dimethylsilane]titanium dimethyl, [(N-benzylamide)(η 5 -indenyl)dimethylsilane]titanium dimethyl, and the like.

[0129] The nickel-based compound is not particularly limited, but specific examples thereof include dibromobistriphenylphosphine nickel, dichlorobistriphenylphosphine nickel, dibromodiacetonitrile nickel, dibromodibenzonitrile nickel, dibromo(1,2-bisdiphenylphosphinoethane)nickel, dibromo(1,3-bisdiphenylphosphinopropane)nickel, dibromo(1,1'-diphenylbisphosphinoferrocene)nickel, dimethylbisdiphenylphosphine nickel, and dimethyl(1,2-bisdiphenylphosphinoethane). Examples of the nickel tetrafluoroborate include nickel, methyl(1,2-bisdiphenylphosphinoethane)nickel tetrafluoroborate, (2-diphenylphosphino-1-phenylethyleneoxy)phenylpyridine nickel, dichlorobistriphenylphosphine palladium, dichlorodibenzonitrile palladium, dichlorodiacetonitrile palladium, dichloro(1,2-bisdiphenylphosphinoethane)palladium, bistriphenylphosphine palladium bistetrafluoroborate, and bis(2,2'-bipyridine)methyliron tetrafluoroborate etherate.

[0130] The hafnium-based compound is not particularly limited, but specifically includes, for example, [(Nt-butylamido)(tetramethyl-η 5-cyclopentadienyl)-1,2-ethanediyl]hafnium dimethyl,[(Nt-butylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]hafnium dimethyl,[(N-methylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]hafnium dimethyl,[(N-phenylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]hafnium dimethyl,[(N-benzylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]hafnium dimethyl,[(Nt-butylamido)(η5- [(N-butylamido)(η5-cyclopentadienyl)dimethylsilane]hafnium dimethyl, [(N-methylamido)(η5-cyclopentadienyl)-1,2-ethanediyl]hafnium dimethyl, [(N-methylamido)(η5-cyclopentadienyl)dimethylsilane]hafnium dimethyl, [(N-butylamido)(η5-indenyl)dimethylsilane]hafnium dimethyl, [(N-benzylamido)(η5-indenyl)dimethylsilane]hafnium dimethyl and the like.

[0131] Further specific examples of the transition metal compound having a cyclic η-bonding anion ligand used in this embodiment include the "dimethyl" portion of the name of each of the zirconium-based compounds and titanium-based compounds listed above (this appears immediately after the end of the name of each compound, i.e., "zirconium" or "titanium" portion, and X in the above formula 9 4 (The name corresponds to the part of the formula (a)) can be used to refer to, for example, "dichloro," "dibromo," "diiodo," "diethyl," "dibutyl," "diphenyl," "dibenzyl," "2-(N,N-dimethylamino)benzyl," "2-butene-1,4-diyl," "s-trans-η 4 -1,4-diphenyl-1,3-butadiene", "s-trans-η 4 -3-Methyl-1,3-pentadiene", "s-trans-η 4 -1,4-dibenzyl-1,3-butadiene", "s-trans-η 4-2,4-Hexadiene", "s-trans-η 4 -1,3-pentadiene", "s-trans-η 4 -1,4-ditolyl-1,3-butadiene", "s-trans-η 4 -1,4-Bis(trimethylsilyl)-1,3-butadiene, s-cis-η 4 -1,4-diphenyl-1,3-butadiene", "s-cis-η 4 -3-methyl-1,3-pentadiene", "s-cis-η 4 -1,4-dibenzyl-1,3-butadiene", "s-cis-η 4 -2,4-hexadiene", "s-cis-η 4 -1,3-pentadiene", "s-cis-η 4 -1,4-ditolyl-1,3-butadiene", "s-cis-η 4 Also included are compounds with names that can be arbitrarily substituted, such as "-1,4-bis(trimethylsilyl)-1,3-butadiene."

[0132] The transition metal compounds having a cyclic η-bonding anion ligand used in this embodiment can be synthesized by a generally known method. In this embodiment, these transition metal compounds may be used alone or in combination.

[0133] Next, the activator (b) capable of reacting with a transition metal compound to form a complex that exhibits catalytic activity (hereinafter, simply referred to as "activator") used in this embodiment will be described. An example of the activator used in this embodiment is a compound defined by the following formula 10. [L 2 -H] d+ [M 5 m Q p ] d- ...Formula 10 (In formula 10, [L 2 -H] d+ represents a proton-donating Bronsted acid, where L 2 represents a neutral Lewis base, d is an integer from 1 to 7; [M 5m Q p ] d- represents a compatible non-coordinating anion, where M 5 represents a metal or metalloid belonging to any one of Groups 5 to 15 of the periodic table, and each Q is independently selected from the group consisting of a hydride, a halide, a dihydrocarbylamide group having 2 to 20 carbon atoms, a hydrocarbyloxy group having 1 to 30 carbon atoms, a hydrocarbon group having 1 to 30 carbon atoms, and a substituted hydrocarbon group having 1 to 40 carbon atoms, wherein the number of Qs that are halides is 1 or less, m is an integer from 1 to 7, p is an integer from 2 to 14, d is as defined above, and pm=d.

[0134] The non-coordinating anion is not particularly limited, but specific examples thereof include tetrakisphenylborate, tri(p-tolyl)(phenyl)borate, tris(pentafluorophenyl)(phenyl)borate, tris(2,4-dimethylphenyl)(hydrophenyl)borate, tris(3,5-dimethylphenyl)(phenyl)borate, tris(3,5-di-trifluoromethylphenyl)(phenyl)borate, tris(pentafluorophenyl)(cyclohexyl)borate, tris(pentafluorophenyl)(naphthyl)borate, tetrakis(pentafluorophenyl)borate, triphenyl(hydroxyphenyl)borate, diphenyl-di(hydroxyphenyl)borate, triphenyl(2,4-dihydroxyphenyl)borate, tri(p-tolyl)borate, tris(pentafluorophenyl)(naphthyl)borate, tris(pentafluorophenyl ... tris(pentafluorophenyl)(hydroxyphenyl)borate, tris(pentafluorophenyl)(hydroxyphenyl)borate, tris(2,4-dimethylphenyl)(hydroxyphenyl)borate, tris(3,5-dimethylphenyl)(hydroxyphenyl)borate, tris(3,5-di-trifluorimethylphenyl)(hydroxyphenyl)borate, tris(pentafluorophenyl)(2-hydroxyethyl)borate, tris(pentafluorophenyl)(4-hydroxybutyl)borate, tris(pentafluorophenyl)(4-hydroxy-cyclohexyl)borate, tris(pentafluorophenyl)(4-(4'-hydroxyphenyl)phenyl)borate, tris(pentafluorophenyl)(6-hydroxy-2-naphthyl)borate, and the like.

[0135] Other preferred examples of non-coordinating anions include borates in which the hydroxy group of the above exemplary borates is replaced with an NHR group, where R is preferably a methyl group, an ethyl group, or a tert-butyl group.

[0136] In addition, the proton-donating Bronsted acid is not particularly limited, but specific examples thereof include trialkyl group-substituted ammonium cations such as triethylammonium, tripropylammonium, tri(n-butyl)ammonium, trimethylammonium, tributylammonium, and tri(n-octyl)ammonium; N,N-dialkylanilinium cations such as N,N-dimethylanilinium, N,N-diethylanilinium, N,N-2,4,6-pentamethylanilinium, and N,N-dimethylbenzylanilinium; dialkylammonium cations such as di-(i-propyl)ammonium and dicyclohexylammonium; triarylphosphonium cations such as triphenylphosphonium, tri(methylphenyl)phosphonium, and tri(dimethylphenyl)phosphonium; and dimethylsulfonium, diethylsulfonium, and diphenylsulfonium.

[0137] In this embodiment, an organometallic oxy compound having a unit represented by the following formula 11 can also be used as the activator. [ka] (Here, in Equation 11, M 6 is a metal or metalloid of Groups 13 to 15 of the periodic table, and R 14 are each independently a hydrocarbon group or a substituted hydrocarbon group having 1 to 12 carbon atoms, and n is a metal M 6 where m is an integer of 2 or greater.)

[0138] A preferred example of the activator used in this embodiment is an organoaluminum oxy compound containing a unit represented by the following formula 12: [ka] (Here, in Equation 12, R 15 is an alkyl group having 1 to 8 carbon atoms, and m is an integer of 2 to 60.

[0139] A more preferred example of the activator used in this embodiment is methylalumoxane containing a unit represented by the following formula 13: [ka] (In formula 13, m is an integer from 2 to 60.) In this embodiment, the activator components may be used alone or in combination.

[0140] In the present embodiment, these catalyst components can also be used as supported catalysts by being supported on a solid component. Such solid components are not particularly limited, but specific examples thereof include at least one inorganic solid material selected from porous polymeric materials such as polyethylene, polypropylene, and styrene-divinylbenzene copolymers; inorganic solid materials of elements in Groups 2, 3, 4, 13, and 14 of the Periodic Table, such as silica, alumina, magnesia, magnesium chloride, zirconia, titania, boron oxide, calcium oxide, zinc oxide, barium oxide, vanadium pentoxide, chromium oxide, and thorium oxide, and mixtures thereof; and double oxides thereof.

[0141] The composite oxide of silica is not particularly limited, but specifically includes, for example, composite oxides of silica, such as silica magnesia and silica alumina, and an element of Group 2 or Group 13 of the periodic table. In addition to the above two catalyst components, an organoaluminum compound can be used as a catalyst component in this embodiment, if necessary. The organoaluminum compound that can be used in this embodiment is, for example, a compound represented by the following formula 14. [ka] (Here, in Equation 14, R 16 is an alkyl group having 1 to 12 carbon atoms or an aryl group having 6 to 20 carbon atoms, and X 5 is a halogen, hydrogen or an alkoxyl group, the alkyl group is linear, branched or cyclic, and n is an integer of 1 to 3.

[0142] Here, the organoaluminum compound may be a mixture of compounds represented by the above formula 14. The organoaluminum compound that can be used in this embodiment is, for example, a compound represented by the above formula R 16 X is a methyl group, an ethyl group, a butyl group, an isobutyl group, a hexyl group, an octyl group, a decyl group, a phenyl group, a tolyl group, etc. 5 Examples of the alkyl group include a methoxy group, an ethoxy group, a butoxy group, and a chlorine group.

[0143] The organoaluminum compound that can be used in the present embodiment is not particularly limited, but specific examples include trimethylaluminum, triethylaluminum, tributylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, tridecylaluminum, and the like, as well as reaction products of these organoaluminum compounds with alcohols such as methyl alcohol, ethyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, octyl alcohol, and decyl alcohol, such as dimethylmethoxyaluminum, diethylethoxyaluminum, and dibutylbutoxyaluminum.

[0144] (Polymerization conditions) The polymerization temperature in the method for producing ultra-high molecular weight polyethylene powder of this embodiment is usually 30°C or higher and 100°C or lower. A polymerization temperature of 30°C or higher tends to enable more efficient industrial production. On the other hand, a polymerization temperature of 100°C or lower tends to enable more continuous and stable operation. In addition, the intrinsic viscosity IV of the ultra-high molecular weight polyethylene powder tends to decrease as the polymerization temperature is increased, and tends to increase as the polymerization temperature is decreased.

[0145] The polymerization pressure in the method for producing the ultra-high molecular weight polyethylene powder of this embodiment is usually normal pressure or more and 2 MPa or less. The polymerization pressure is preferably 0.1 MPa or more, more preferably 0.12 MPa or more, and is preferably 1.5 MPa or less, more preferably 1.0 MPa or less. A polymerization pressure of normal pressure or more tends to enable industrially more efficient production, and a polymerization pressure of 2 MPa or less tends to suppress partial heat generation due to a rapid polymerization reaction when the catalyst is introduced, and polyethylene tends to be produced stably.

[0146] The polymerization reaction can be carried out in any of a batch system (batch system), semi-continuous system, and continuous system. From the viewpoint of controlling the voids of the ultra-high molecular weight polyethylene powder of the present embodiment within the above-mentioned range, a batch system (batch system) is preferred. On the other hand, from the viewpoint of making the polymerization system more uniform, a continuous system is preferred. By continuously supplying ethylene gas, a solvent, a catalyst, and the like into the polymerization system and continuously discharging them together with the produced polyethylene, it is possible to suppress a partial high temperature state caused by a sudden reaction of ethylene, and the polymerization system is more stabilized. When ethylene reacts in a uniform state within the system, the generation of branches and double bonds in the polymer chain is suppressed, and the molecular weight of polyethylene is reduced and crosslinking is less likely to occur, so that the amount of unmelted material remaining when the ultra-high molecular weight polyethylene powder is melted or dissolved is reduced, coloring is suppressed, and problems such as a decrease in mechanical properties are less likely to occur.

[0147] It is also possible to carry out the polymerization in two or more stages with different reaction conditions. Furthermore, as described in, for example, West German Patent Application Publication No. 3127133, the intrinsic viscosity of the resulting polyethylene can be adjusted by making hydrogen present in the polymerization system or by changing the polymerization temperature. By adding hydrogen as a chain transfer agent to the polymerization system, it is possible to control the intrinsic viscosity within an appropriate range. By adding a chain transfer agent, the intrinsic viscosity IV of the ultra-high molecular weight polyethylene produced at the same polymerization temperature tends to be lower. When hydrogen is added to the polymerization system, the molar fraction of hydrogen is preferably 0 mol% or more and 30 mol% or less, more preferably 0 mol% or more and 25 mol% or less, and even more preferably 0 mol% or more and 20 mol% or less. In this embodiment, in addition to the above-mentioned components, other known components useful for the production of polyethylene can be included.

[0148] As described above, it is important that the ultra-high molecular weight polyethylene powder of this embodiment is immersed in liquid paraffin, and left to stand for 1 to 6 hours under vacuum (300 to 400 Pa) while applying a temperature (50 to 100°C) at which the powder does not melt and at which the molecular chains can move, allowing the liquid paraffin to sufficiently penetrate into the powder pores and gradually untangling the molecular chains over time. Next, the powder is immersed in hexane for 5 to 24 hours to extract the liquid paraffin from the powder, and dried at 25 to 50°C for 24 hours, thereby obtaining a powder with a short dissolution time (5 to 80 seconds) (control method 1). In addition, a powder with a short dissolution time (5 seconds or more and 80 seconds or less) can be obtained by adding 55 to 70 mass% liquid paraffin to the polymerization solvent during prepolymerization, polymerizing the polymer obtained by using the polymer as a prepolymerization catalyst, and then removing the liquid paraffin from the powder after completion of polymerization (Control Method 2). Furthermore, by carrying out polymerization under high pressure (0.5 MPa to 1.0 MPa) conditions using a prepolymerization catalyst (low temperature (5°C to 20°C) and short time (0.5 hours to 2 hours) polymerization and an ethylene charge amount (5 NL to 20 NL), the polymerization can be carried out with high initial polymerization activity. Therefore, in the polymerization process, a large amount of polymerization heat energy is generated, and in the process of this heat energy escaping from the center of the powder to the outside, continuous pores are formed that extend from the center of the powder to the surface, and the diameter of the continuous pores can be controlled by adjusting the amount of this heat energy (control method 3).

[0149] When polymerizing the ultra-high molecular weight polyethylene powder of this embodiment, an antistatic agent such as Stadis or STATSAFE manufactured by Innospec (distributor: Maruwa Bussan) can be used to suppress electrostatic adhesion of the polymer to the polymerization reactor. The antistatic agent such as Stadis or STATSAFE can be diluted in an inert hydrocarbon medium and added to the polymerization reactor by a pump or the like. The amount of addition in this case is preferably 1 ppm or more and 500 ppm or less, more preferably 10 ppm or more and 100 ppm or less, based on the amount of ethylene polymer produced per unit time, such as by adding the agent to the solid catalyst in advance or adding the agent to the polymerization reactor.

[0150] [Additives] Additives such as slip agents, neutralizing agents, antioxidants, light resistance stabilizers, antistatic agents, and pigments may be added to the ultra-high molecular weight polyethylene powder of this embodiment as necessary.

[0151] The slip agent or neutralizing agent is not particularly limited, but may be, for example, an aliphatic hydrocarbon, a higher fatty acid, a higher fatty acid metal salt, a fatty acid ester of alcohol, a wax, a higher fatty acid amide, a silicone oil, or a rosin. A specific example may be, but is not particularly limited, calcium stearate. The content of the slip agent or neutralizing agent is not particularly limited, but is preferably 5000 ppm or less, more preferably 4000 ppm or less, and even more preferably 3000 ppm or less.

[0152] The antioxidant is not particularly limited, but for example, a phenol-based compound or a phenol-phosphate-based compound is preferable. Specific examples of the antioxidant include phenol-based antioxidants such as 2,6-di-t-butyl-4-methylphenol (dibutylhydroxytoluene), n-octadecyl-3-(4-hydroxy-3,5-di-t-butylphenyl)propionate, and tetrakis(methylene(3,5-di-t-butyl-4-hydroxyhydrocinnamate))methane; phenol-phosphorus-based antioxidants such as 6-[3-(3-t-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-t-butyldibenzo[d,f][1,3,2]dioxaphosphepine; and phosphorus-based antioxidants such as tetrakis(2,4-di-t-butylphenyl)-4,4'-biphenylene-diphosphonite, tris(2,4-di-t-butylphenyl)phosphite, and cyclic neopentanetetraylbis(2,4-t-butylphenylphosphite).

[0153] In the ultra-high molecular weight polyethylene powder according to this embodiment, the amount of the antioxidant is preferably 5 parts by mass or less, more preferably 4 parts by mass or less, even more preferably 3 parts by mass or less, and particularly preferably 2 parts by mass or less, when the total amount of the ultra-high molecular weight polyethylene powder and liquid paraffin is 100 parts by mass. When the amount of the antioxidant is 5 parts by mass or less, deterioration of the polyethylene is suppressed, and embrittlement, discoloration, deterioration of mechanical properties, etc. are less likely to occur, resulting in more excellent long-term stability.

[0154] Examples of the light resistance stabilizer include, but are not limited to, benzotriazole-based light resistance stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; and hindered amine-based light resistance stabilizers such as bis(2,2,6,6-tetramethyl-4-piperidine)sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}]. The content of the light resistance stabilizer is not particularly limited, but is 5000 ppm or less, preferably 3000 ppm or less, and more preferably 2000 ppm or less.

[0155] The antistatic agent is not particularly limited, but examples thereof include aluminosilicates, kaolin, clay, natural silica, synthetic silica, silicates, talc, diatomaceous earth, and glycerin fatty acid esters.

[0156] As a method for separating the solvent in the polymerization step of the polyethylene powder of this embodiment, any of a decantation method, a centrifugal separation method, a filter filtration method, etc. can be used, but a filter filtration method which easily separates the ethylene polymer from the solvent is preferred.

[0157] The method for deactivating the catalyst used in the polymerization step of the ethylene-based polymer constituting the polyethylene powder of the present embodiment is not particularly limited, but the catalyst is preferably deactivated after the ethylene-based polymer is separated from the solvent.

[0158] By introducing an agent for deactivating the catalyst after separating the polyethylene powder from the solvent, it is possible to suppress precipitation of low-molecular-weight components, catalyst components, and the like contained in the solvent in the ethylene polymer.

[0159] The agent for deactivating the catalyst is not particularly limited, but examples thereof include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, alkynes, and the like.

[0160] In the method for producing the polyethylene powder of the present embodiment, it is preferable to carry out a drying step after separating the ethylene polymer from the solvent. In the drying step, it is preferable to use a rotary kiln method, a paddle method, a fluidized bed dryer, or the like. The drying temperature is preferably 30° C. or more and 150° C. or less.

[0161] It is also effective to introduce an inert gas such as nitrogen into the dryer to accelerate drying. In this case, it is even more effective to use steam or the like as a catalyst deactivating agent.

[0162] After drying the ethylene polymer constituting the polyethylene powder of the present embodiment, it may be sieved to remove coarse particles.

[0163] The polyethylene powder of the present embodiment may be a mixture of multiple polyethylene powders containing ethylene polymers obtained by the above-mentioned production method.

[0164] [Molded body] The ultra-high molecular weight polyethylene powder of this embodiment can be molded by various methods. The molded article of this embodiment is obtained by molding the ultra-high molecular weight polyethylene powder described above. The molded article of this embodiment can be used for various applications. Specific examples of the molded article of this embodiment include, but are not limited to, separators for secondary batteries (e.g., microporous membranes) and fibers (e.g., high-strength fibers), and among these, the molded article is suitable as a microporous membrane and high-strength fiber for lithium-ion secondary battery separators.

[0165] The method for producing the molded article of the present embodiment may be a conventionally known method, and examples of such a method include, but are not limited to, compression molding (press molding), extrusion molding, stretch molding, etc. In addition, when the molded article is a separator for a secondary battery or a fiber, the manufacturing method is as follows.

[0166] The method for producing a separator for a secondary battery (e.g., a microporous membrane) is not particularly limited, but for example, a processing method using a solvent in a wet process in which an extruder equipped with a T-die is used for extrusion, stretching, extraction, and drying. Specifically, for example, the method is not particularly limited, but for example, a manufacturing method under the following general swelling conditions and a manufacturing method under the following low-temperature swelling conditions.

[0167] (Swelling conditions) Ultra-high molecular weight polyethylene powder is mixed with liquid paraffin, and additives such as antioxidants are added as necessary. The melting point (T m2 ) and stir at a temperature 35°C lower than the recommended temperature to prepare a slurry liquid. The obtained slurry liquid is put into a kneading machine, kneaded at a constant temperature, and then hot-pressed and cold-pressed to form a gel sheet. The thickness of the gel sheet is adjusted by using a metal frame. The gel-like sheet is stretched using a simultaneous biaxial stretching machine, and the stretched film is cut out and fixed on a metal frame. It is then immersed in hexane to extract and remove the liquid paraffin, and then dried. It is further heat-set to obtain a microporous membrane for a secondary battery separator.

[0168] The method for producing fibers (e.g., high-strength fibers) is not particularly limited, but examples thereof include a method in which liquid paraffin and the above-mentioned ultra-high molecular weight polyethylene powder are mixed and spun, followed by heating and drawing.Specific examples thereof include, but are not particularly limited to, a production method under the following general swelling conditions and a production method under the following low-temperature swelling conditions.

[0169] (Swelling conditions) Ultra-high molecular weight polyethylene powder is mixed with liquid paraffin, and additives such as antioxidants are added as necessary. The melting point (T m2 ) and stir at a temperature 35°C lower than the recommended temperature to prepare a slurry liquid. Next, the slurry liquid is charged into a kneading machine and kneading is carried out at a constant temperature. The mixture is then spun through a spinneret attached to a Capillograph 1D. At this time, the yarn containing the discharged liquid paraffin is wound up at a location away from the spinneret. Next, in order to remove the liquid paraffin from the wound yarn, the yarn is immersed in hexane for extraction, and then dried. The obtained yarn is first drawn in a thermostatic chamber, and then secondly drawn in the thermostatic chamber until the yarn breaks, to obtain a high-strength fiber (drawn yarn).

[0170] [High-strength fiber] Specific examples of the manufacturing method of high strength fibers include a manufacturing method including a slurry process, a gelling process, an optional kneading process, an optional extrusion preparation process, an extrusion process, an optional quenching process, an extraction process, and a raw yarn drawing process.

[0171] (Slurry process) The slurry process is a process in which the above-mentioned ultra-high molecular weight polyethylene powder is mixed with a first liquid paraffin, and the mixture is stirred at a temperature equal to or lower than the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry.

[0172] The stirring temperature is preferably 25°C or higher and 120°C or lower, more preferably 50°C or higher and 115°C or lower, even more preferably 80°C or higher and 110°C or lower, and particularly preferably 90°C or higher and 105°C or lower. By setting the stirring temperature at 25°C or higher, the liquid paraffin can be efficiently impregnated into the pores of the ultra-high molecular weight polyethylene powder. In addition, by setting the temperature at 120°C or lower, melting of the surface of the ultra-high molecular weight polyethylene powder is suppressed, and fusion of the powder particles is prevented, resulting in a uniform gel with entangled molecular chains that have been untangled.

[0173] (Gelling process) The gelling step is a step of mixing the slurry with a second liquid paraffin at 150°C or more and 300°C or less to obtain a gel for yarn at 140°C or more and 200°C or less. By setting the temperature of the gel for yarn at 140℃ or higher, it is possible to obtain a uniform gel in which the molecular chains are untangled in a short time. Also, by setting the temperature at 200℃ or lower, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0174] The temperature of the second liquid paraffin is preferably 150°C or more and 250°C or less, more preferably 150°C or more and 200°C or less, and further preferably 150°C or more and 180°C or less.

[0175] The temperature of the yarn gel is preferably 140°C or higher and 190°C or lower, more preferably 140°C or higher and 180°C or lower, and even more preferably 140°C or higher and 170°C or lower.

[0176] The polyethylene concentration of the yarn gel is preferably 3% by mass or more and 20% by mass or less, more preferably 3% by mass or more and 15% by mass or less, even more preferably 3% by mass or more and 10% by mass or less, and particularly preferably 3% by mass or more and 8% by mass or less. By making the polyethylene concentration of the yarn gel 3% by mass or more, it is possible to stably spin yarn with little unevenness in the yarn diameter. Also, by making it 20% by mass or less, it is possible to obtain yarn with untangled molecular chains.

[0177] (Kneading process) The kneading step is a step of kneading the gel for yarn.

[0178] The kneading temperature is preferably 140°C or more and 200°C or less, more preferably 140°C or more and 180°C or less, still more preferably 140°C or more and 170°C or less, and particularly preferably 150°C or more and 160°C or less. By setting the kneading temperature at 140°C or higher, it is possible to obtain a uniform gel in which the molecular chains are untangled. Also, by setting the temperature at 200°C or lower, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0179] The kneading time is preferably from 5 to 180 minutes, more preferably from 10 to 150 minutes, further preferably from 15 to 90 minutes, and particularly preferably from 30 to 60 minutes. By kneading for 5 minutes or more, it is possible to obtain a uniform gel in which the molecular chains are untangled, while by kneading for 180 minutes or less, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0180] The kneading rotation speed is preferably 3 rpm or more and 50 rpm or less, more preferably 3 rpm or more and 30 rpm or less, further preferably 3 rpm or more and 20 rpm or less, and particularly preferably 3 rpm or more and 10 rpm or less. By setting the kneading speed at 3 rpm or more, it is possible to obtain a uniform gel in which the molecular chains are untangled, while by setting the speed at 50 rpm or less, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0181] (Extrusion preparation process) The extrusion preparation step is a step of preparing the gel for extrusion. Specific examples of the extrusion preparation include temperature adjustment and degassing the gel for extrusion.

[0182] The temperature in the extrusion preparation step is preferably 140°C or more and 200°C or less, more preferably 140°C or more and 190°C or less, even more preferably 140°C or more and 180°C or less, and particularly preferably 150°C or more and 180°C or less. By setting the temperature in the extrusion preparation process at 140°C or higher, it is possible to prevent the outflow of liquid paraffin from the gel for raw yarn and suppress fluctuations in the gel concentration, thereby enabling stable production of raw yarn. In addition, by setting the temperature at 200°C or lower, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0183] The time for the extrusion preparation step (e.g., the degassing time) is preferably from 5 to 90 minutes, more preferably from 5 to 60 minutes, even more preferably from 15 to 60 minutes, and particularly preferably from 30 to 60 minutes. By setting the extrusion preparation time to 5 minutes or more, the gel for the raw yarn can be sufficiently degassed and the raw yarn can be obtained stably. Also, by setting the time to 90 minutes or less, a significant decrease in molecular weight due to thermal decomposition can be suppressed.

[0184] (Extrusion process) The extrusion step is a step of extruding the yarn gel to obtain yarn.

[0185] The extrusion speed is preferably 5 mm / min to 20 mm / min, more preferably 5 mm / min to 15 mm / min, even more preferably 7.5 mm / min to 12 mm / min, and particularly preferably 7.5 mm / min to 10 mm / min. By setting the extrusion speed at 5 mm / min or more, the raw yarn can be collected without applying tension, and in the raw yarn drawing process, it can be drawn to a high ratio, resulting in highly oriented (high strength) yarn. In addition, by setting the speed at 20 mm / min or less, the discharge amount can be stabilized, and raw yarn with little unevenness in the yarn diameter can be stably obtained.

[0186] The winding speed is preferably 200 mm / min or more and 1600 mm / min or less, more preferably 200 mm / min or more and 1400 mm / min or less, even more preferably 250 mm / min or more and 1000 mm / min or less, and particularly preferably 500 mm / min or more and 800 mm / min or less. By setting the winding speed at 200 mm / min or more, the raw yarn can be recovered without applying tension, and in the raw yarn drawing process, the raw yarn can be drawn to a high ratio, resulting in a highly oriented (high strength) yarn. In addition, by setting the speed at 1600 mm / min or less, the discharge amount can be stabilized, and raw yarn with little unevenness in the yarn diameter can be stably obtained.

[0187] The discharge rate is preferably 0.2 g / min or more and 1.5 g / min or less, more preferably 0.2 g / min or more and 1.2 g / min or less, even more preferably 0.2 g / min or more and 1.0 g / min or less, and particularly preferably 0.3 g / min or more and 0.8 g / min or less. By setting the discharge rate at 0.2 g / min or more, the raw yarn can be collected without applying tension, and in the raw yarn drawing process, it can be drawn to a high ratio, resulting in highly oriented (high strength) yarn. In addition, by setting the discharge rate at 1.5 g / min or less, melt fracture can be suppressed, and raw yarn with little unevenness in yarn diameter can be stably obtained.

[0188] The spinning hole diameter is preferably 0.8 mm or more and 1.5 mm or less, more preferably 0.8 mm or more and 1.2 mm or less, further preferably 0.8 mm or more and 1.0 mm or less, and particularly preferably 0.9 mm or more and 1.0 mm or less. By making the diameter of the spinneret 0.8mm or more, it is possible to adjust the diameter of the raw yarn after the liquid paraffin extraction to a certain degree, and by drawing the raw yarn to a high ratio in the raw yarn drawing process, a highly oriented (high strength) yarn can be obtained. Also, by making the diameter 1.5mm or less, it is possible to shorten the time required to extract the liquid paraffin from the raw yarn, and the extraction process can be completed efficiently.

[0189] (Quenching process) The quenching step is a step of quenching the raw yarn. The quenching method is not particularly limited, but may be, for example, a method of passing the raw yarn through a water bath.

[0190] The time from the extrusion step to the quenching step (for example, the time until the extruded raw yarn enters a water bath) is preferably 0 s or more and 10 s or less, more preferably 0 s or more and 5 s or less, and even more preferably 0 s or more and 2 s or less. By keeping the time from the extrusion process to the quenching process to 10 seconds or less, the molten raw yarn is rapidly cooled and solidified, minimizing unevenness in the raw yarn diameter.

[0191] When the raw yarn is passed through a water bath in the quenching step, the distance from the spinneret to the water surface of the water bath is preferably 0 cm or more and 10 cm or less, more preferably 1 cm or more and 8 cm or less, even more preferably 1 cm or more and 5 cm or less, and particularly preferably 1 cm or more and 3 cm or less. By keeping the distance from the spinneret to the water bath surface at 10 cm or less, the molten yarn is rapidly cooled and solidified, minimizing unevenness in the yarn diameter.

[0192] The temperature in the quenching step is preferably 5°C or more and 30°C or less, more preferably 5°C or more and 25°C or less, even more preferably 5°C or more and 20°C or less, and particularly preferably 5°C or more and 15°C or less. By setting the temperature in the quenching process at 5°C or higher, cooling costs can be reduced and production can be made efficient. In addition, by setting the temperature at 30°C or lower, the molten raw yarn can be rapidly cooled and solidified, minimizing unevenness in the raw yarn diameter.

[0193] (extraction process) The extraction step is a step of extracting the first liquid paraffin and the second liquid paraffin from the raw yarn to obtain a raw yarn for drawing.

[0194] To extract the liquid paraffin, it is preferable to use an extraction solvent, which includes, but is not limited to, hexane and dichloromethane.

[0195] The extraction method is not particularly limited, but may be, for example, a method in which the raw yarn is immersed in an extraction solvent.

[0196] The extraction time is preferably from 3 hours to 24 hours, more preferably from 3 hours to 20 hours, even more preferably from 5 hours to 20 hours, and particularly preferably from 10 hours to 20 hours. By setting the extraction time to 3 hours or more, liquid paraffin can be extracted to an extent that does not cause problems for raw yarn for drawing. If a large amount of liquid paraffin remains in the raw yarn for drawing, when heat is applied in the raw yarn drawing process, the molecular chains have high mobility and are easily highly oriented, but this state is difficult to maintain (they tend to return to the state before high orientation). Therefore, it is difficult to obtain a high-strength yarn. In addition, by setting the extraction time to 24 hours or less, raw yarn for drawing can be obtained efficiently without reducing productivity.

[0197] (Yarn drawing process) The raw yarn drawing step is a step of heating and drawing the raw yarn to be drawn.

[0198] The stretching is preferably a multi-stage stretching, more preferably a two-stage stretching, which preferably includes a first stretching step and a second stretching step.

[0199] ((1st stretching process)) The delivery speed is preferably 50 mm / min or more and 200 mm / min or less, more preferably 50 mm / min or more and 150 mm / min or less, even more preferably 50 mm / min or more and 120 mm / min or less, and particularly preferably 50 mm / min or more and 100 mm / min or less.

[0200] The winding speed is preferably 1000 mm / min or more and 4000 mm / min or less, more preferably 1000 mm / min or more and 3500 mm / min or less, even more preferably 1500 mm / min or more and 3500 mm / min or less, and particularly preferably 2000 mm / min or more and 3000 mm / min or less. The stretching ratio is controlled by adjusting the delivery speed and the winding speed, and is set while taking productivity into consideration.

[0201] The stretching temperature is preferably 110°C or more and 155°C or less, more preferably 110°C or more and 150°C or less, further preferably 115°C or more and 145°C or less, and particularly preferably 120°C or more and 140°C or less. By setting the drawing temperature at 110°C or higher, it is possible to draw the fibers while keeping the molecular chains in a highly mobile state, resulting in a highly oriented fiber. By setting the drawing temperature at 155°C or lower, the fibers can be drawn without melting.

[0202] ((Second stretching process)) The delivery speed is preferably 50 mm / min or more and 200 mm / min or less, more preferably 50 mm / min or more and 150 mm / min or less, even more preferably 50 mm / min or more and 120 mm / min or less, and particularly preferably 50 mm / min or more and 100 mm / min or less.

[0203] The winding speed is preferably 100 mm / min or more and 500 mm / min or less, more preferably 100 mm / min or more and 450 mm / min or less, even more preferably 150 mm / min or more and 400 mm / min or less, and particularly preferably 200 mm / min or more and 300 mm / min or less. The stretching ratio is controlled by adjusting the delivery speed and the winding speed, and is set while taking productivity into consideration.

[0204] The stretching temperature is preferably 130°C or more and 155°C or less, more preferably 130°C or more and 150°C or less, further preferably 135°C or more and 150°C or less, and particularly preferably 140°C or more and 150°C or less. By setting the drawing temperature at 130°C or higher, it is possible to draw the fibers while keeping the molecular chains in a highly mobile state, resulting in a highly oriented fiber. By setting the drawing temperature at 155°C or lower, the fibers can be drawn without melting the first drawn yarn.

[0205] [Microporous membrane] Specific examples of the method for producing the microporous membrane include a method including a slurry step, a gelling step, an optional kneading step, a pressing step, a membrane stretching step, and an extraction step.

[0206] (Slurry process) The slurry process is a process in which the above-mentioned ultra-high molecular weight polyethylene powder is mixed with a first liquid paraffin, and the mixture is stirred at a temperature equal to or lower than the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry.

[0207] The stirring temperature is preferably 25°C or higher and 120°C or lower, more preferably 50°C or higher and 115°C or lower, even more preferably 80°C or higher and 110°C or lower, and particularly preferably 90°C or higher and 105°C or lower. By setting the stirring temperature at 25°C or higher, the liquid paraffin can be efficiently impregnated into the pores of the ultra-high molecular weight polyethylene powder. In addition, by setting the temperature at 120°C or lower, melting of the surface of the ultra-high molecular weight polyethylene powder is suppressed, and fusion of the powder particles is prevented, resulting in a uniform gel with entangled molecular chains that have been untangled.

[0208] (Gelling process) The gelling step is a step of mixing the slurry with a second liquid paraffin at 150°C or more and 300°C or less to obtain a gel for pressing at 140°C or more and 200°C or less. By setting the temperature of the gel for pressing at 140°C or higher, it is possible to obtain a uniform gel in which the molecular chains are untangled in a short time. In addition, by setting the temperature at 200°C or lower, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0209] The temperature of the second liquid paraffin is preferably 160°C or more and 210°C or less, more preferably 170°C or more and 200°C or less, and even more preferably 180°C or more and 200°C or less.

[0210] The polyethylene concentration of the pressing gel is preferably 20% by mass or more and 55% by mass or less, more preferably 20% by mass or more and 50% by mass or less, even more preferably 20% by mass or more and 40% by mass or less, and particularly preferably 20% by mass or more and 30% by mass or less. By making the polyethylene concentration of the press gel 20% by mass or more, it is possible to stably produce a press sheet with little unevenness in thickness. Also, by making it 55% by mass or less, it is possible to obtain a press sheet with untangled molecular chains.

[0211] (Kneading process) The kneading step is a step of kneading the press gel.

[0212] The kneading temperature is preferably 140°C or more and 250°C or less, more preferably 150°C or more and 240°C or less, further preferably 160°C or more and 230°C or less, and particularly preferably 180°C or more and 220°C or less. By setting the kneading temperature at 140°C or higher, it is possible to obtain a uniform gel in which the molecular chains are untangled. Also, by setting the temperature at 250°C or lower, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0213] The kneading time is preferably from 5 to 60 minutes, more preferably from 5 to 40 minutes, further preferably from 5 to 30 minutes, and particularly preferably from 5 to 20 minutes. By kneading for 5 minutes or more, it is possible to obtain a uniform gel in which the molecular chains are untangled, while by kneading for 60 minutes or less, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0214] The kneading rotation speed is preferably 30 rpm or more and 100 rpm or less, more preferably 30 rpm or more and 80 rpm or less, further preferably 30 rpm or more and 70 rpm or less, and particularly preferably 30 rpm or more and 60 rpm or less. By setting the kneading speed at 30 rpm or more, it is possible to obtain a uniform gel in which the molecular chains are untangled, while by setting the speed at 100 rpm or less, it is possible to prevent a significant decrease in molecular weight due to thermal decomposition.

[0215] (Pressing process) The pressing step is a step of hot pressing the gel for pressing to obtain a gel sheet.

[0216] In the pressing step, it is preferable to use a metal frame of 1.0 mm so that the thickness of the gel sheet becomes 1.0 mm.

[0217] In the pressing step, it is preferable to perform pressing while adjusting the temperature and pressure in multiple stages (preferably three stages). For example, In the first stage, the temperature is between 180℃ and 220℃, the pressure is 1MPa, and the time is 3 minutes. In the second stage, the temperature is between 180℃ and 220℃, the pressure is 10MPa, and the time is 2 minutes. In the third stage, it is preferable to cool the mixture under conditions of a temperature of 20° C. to 35° C., a pressure of 10 MPa, and a time of 5 minutes.

[0218] (Membrane stretching process) The membrane stretching step is a step of stretching the gel sheet to obtain a stretched membrane.

[0219] The stretching is preferably simultaneous biaxial stretching.

[0220] The stretching temperature is preferably 110°C or higher and 130°C or lower. By setting the stretching temperature at 110°C or higher, it is possible to stretch the gel sheet while the molecular chains are in a state of high mobility, resulting in high orientation. By setting the stretching temperature at 130°C or lower, the gel sheet can be stretched without melting.

[0221] The stretching ratio in the machine direction is preferably 5 times or more and 20 times or less, more preferably 7 times or more and 18 times or less, and further preferably 10 times or more and 16 times or less.

[0222] The stretching ratio in the transverse direction is preferably 5 times or more and 20 times or less, more preferably 7 times or more and 18 times or less, and further preferably 10 times or more and 16 times or less. The stretching ratio is set taking into consideration the strength of the film and productivity.

[0223] (extraction process) The extraction step is a step of extracting the first liquid paraffin and the second liquid paraffin from the stretched membrane.

[0224] To extract the liquid paraffin, it is preferable to use an extraction solvent, which includes, but is not limited to, hexane and dichloromethane.

[0225] The extraction method is not particularly limited, but may be, for example, a method in which the stretched membrane is immersed in an extraction solvent.

[0226] The extraction time is preferably from 3 hours to 24 hours, more preferably from 3 hours to 20 hours, further preferably from 5 hours to 20 hours, and particularly preferably from 10 hours to 20 hours. EXAMPLES

[0227] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the following examples in any way.

[0228] Here, the ethylene and hexane used in the examples and comparative examples were dehydrated using MS-3A (manufactured by Showa Union), and hexane was further deoxygenated by degassing under reduced pressure using a vacuum pump before use.

[0229] The liquid paraffin used in the examples and comparative examples was liquid paraffin manufactured by MORESCO Corporation (product name: Sumoil P-350P). The typical properties are density at 15°C: 0.866 g / cm 3 , pour point: -10℃, kinematic viscosity 40℃: 68.00mm 2 / s (cSt), kinematic viscosity at 100°C: 9.188 mm2 / s (cSt), ring analysis Cn: 30%, Cp: 70%, average molecular weight: 489 g / mol.

[0230] [Measurement method and conditions] The physical properties of the ultra-high molecular weight polyethylene powders of the Examples and Comparative Examples were measured by the following methods.

[0231] (Measurement 1) Intrinsic viscosity IV The intrinsic viscosity IV of the ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples was measured in accordance with ISO1628-3 (2010) as follows. Polyethylene powder was weighed in the range of 4.0 to 4.5 mg, and 20 mL of decahydronaphthalene (2,6-di-t-butyl-4-methylphenol was added at 1 g / L, hereinafter referred to as decalin) was used as a solvent, which had been degassed with a vacuum pump and replaced with nitrogen. The solution was dissolved by stirring for 90 minutes at 150 ° C in a dissolution tube in which the air inside had been degassed with a vacuum pump and replaced with nitrogen to obtain a solution. A Cannon-Fenske viscometer (manufactured by Shibata Scientific Instruments Co., Ltd.: product number -100) was used as the viscosity tube. This operation was repeated five times, and the average value of the three points excluding the maximum and minimum values ​​was calculated, and the final limiting viscosity was calculated.

[0232] (Measurement 2) Dissolution time The dissolution times of the ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples were calculated by carrying out the following procedures 1 and 2 in order. [Step 1; Calculation of D50] The particle size of the target ultra-high molecular weight polyethylene powder was measured using a laser particle size distribution analyzer (SALD-2100, manufactured by Shimadzu Corporation) with methanol as the dispersion medium, and a cumulative particle size distribution was created from the small particle size side based on the measurement, and the particle size at the cumulative 50% was defined as D50. This operation was repeated five times, and the average value of the three points excluding the maximum and minimum values ​​was calculated to calculate the final D50. [Step 2: Calculating dissolution time] The dissolution time of a powder with a particle diameter of D50 is obtained. First, one ultra-high molecular weight polyethylene powder whose major axis diameter and minor axis diameter (the shortest distance between parallel lines in the plane diagram of the particle observed using an optical microscope is the minor axis diameter of the particle, and the longest distance between parallel lines perpendicular to the shortest distance is the major axis diameter of the particle) is arbitrarily collected while checking with an optical microscope. One collected ultra-high molecular weight polyethylene powder particle (hereinafter also referred to as "measurement particle") is set on a slide glass, 0.05 mL of liquid paraffin is dripped onto the measurement particle using a 1 mL syringe, and then a cover glass is placed on the measurement particle to sandwich the measurement particle. Then, the slide glass is set on a heat stage and the temperature is raised from room temperature to 150°C under the following heating conditions. The appearance of the measurement particle during heating is photographed every 5 seconds with an optical microscope equipped with a camera. The circle equivalent diameter of the measurement particle is calculated from each obtained observation image, and the time from the state where the circle equivalent diameter is the largest to the disappearance of the powder is taken as the dissolution time. This procedure was repeated 10 times, and the maximum and minimum values ​​were excluded to calculate the average value of the remaining 8 values, from which the final dissolution time was calculated. (Temperature rise conditions) Heating rate from room temperature to 35℃: 5℃ / min Heating rate in the range of 35℃~80℃: 8℃ / min Heating rate in the range of 80℃~150℃: 5℃ / min

[0233] (Measurement 3) Percentage of open pores in powder with particle size D50 The ratio of continuous pores in the ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples was calculated according to the following procedure 3. [Step 3; Percentage of communicating holes] Five grains of ultra-high molecular weight polyethylene powder with major and minor axis diameters (the shortest distance between parallel lines in the plan view of the particle observed using an optical microscope is the minor axis diameter of the particle, and the longest distance between parallel lines in the direction perpendicular to that is the major axis diameter of the particle) within the range of D50±10% were taken, and double-sided tape was attached to a sample stage, and the five grains of powder were placed on top of the tape. Next, the powder was irradiated with X-rays using a nano3DX (manufactured by Rigaku Corporation), and 3D image data was captured. The image was then processed using image analysis software to calculate the percentage of interconnected pores. The X-ray and imaging conditions were as follows:

[0234] [X-ray conditions] X-ray target: Cu X-ray tube voltage / current: 40kV / 30mA [Shooting conditions] 180° rotation Number of projections: 1000 Exposure time: 10 seconds / frame Spatial resolution: 0.54μm / pix

[0235] The captured images were then analyzed using analysis software. The captured images and their tomographic images are shown in Figures 1 and 2. [Analysis range] The analysis range was the area where the powder did not come into contact with the adhesive of the double-sided tape in the vertical direction relative to the horizontal surface of the sample stage.

[0236] [Procedure for detecting resin areas] Noise removal part 1 1. ImageJ's Median3D was applied to the X-ray CT images. The parameters were set to x=2, y=2, Z=2. Morphological Filters (3D) from MorphLibJ were applied to the results of 2.1. The parameters were set to operation=Closing, element=Ball, x-radius=2, y-radius=2, z-radius=2. The results of 3.2 were applied with ImageJ's Gaussian Blur3D. The parameters were set to x=2, y=2, Z=2.

[0237] Threshold For the results of 4.3, voxels with intensity values ​​above the threshold were marked white, and voxels below the threshold were marked black. To estimate the threshold, we used ImageJ's implementation of the moment method.

[0238] Noise removal part 2 For the results of 5.4, white voxels were divided into contiguous voxel clusters, and clusters smaller than 1000 voxels were changed to black. The clustering process was carried out using 3D Simple Segmentation in 3D Suite ImageJ. The black and white voxel data obtained in the process of 5 was designated as P. The white area in P was designated as the resin area (A).

[0239] [Procedure for detecting closed pore areas] 6.3D Suite ImageJ's 3D Fill Holes was applied to P. 7.The voxels resulting from 6 that are in the same position as the white voxels in P are made black. The black and white voxel data obtained by processing 7 was designated as Q. The white areas in Q were designated as closed pore areas (B).

[0240] [Procedure for detecting particle outline] 8.3D Suite Using the 3D DistanceMap in ImageJ, the distance to the nearest white voxel was determined for each voxel in P. The parameters were set as map=EDT,mask=None,threshold=1,inverse. Voxels with a result of 9.8 of 20 or less were newly designated as white, and all other voxels were designated as black. 10. ImageJ's 2D Fill Holes was applied to the bottom cross-sectional image in the analysis range. 11. 3D Fill Holes from 3D Suite ImageJ was applied to the entire surface. 12.3D Suite ImageJ's 3D DistanceMap was used to determine the distance to the nearest black voxel for each of the 11 resulting voxels with the following parameters: map=EDT, mask=None, threshold=1, inverse. Voxels with a result of 13.12 of 20 or less were newly designated as black, and other voxels were designated as white. The black and white voxel data of the result of 13 was designated as R. The white area in R was designated as the particle outline (C).

[0241] [Procedure for detecting the area of ​​communicating holes] 14.The voxel in R that is in the same position as the white voxel in Q is made black. 15.The voxels of the result 14 that are in the same position as the white voxels of P were made black. The black and white voxel data of the result of 15 was designated as S. The white area in S was designated as the area of ​​the communicating hole (D). [Open pore area (D)] = [Particle outer shape (C)] - [Closed pore area (B)] - [Resin area (A)]

[0242] [Ratio of interconnected holes] Percentage of interconnected holes = total number of white voxels in S / total number of white voxels in R This series of operations was carried out for five powder particles, and the average value was taken as the final percentage of interconnected pores.

[0243] (Measurement 4) Surface thickness of powder with particle size D50 The surface thickness of the ultra-high molecular weight polyethylene powder obtained in the Examples and Comparative Examples was calculated according to the following procedure 4. [Step 4; Powder surface thickness] 16.The thickness of P was calculated using BoneJ. 17.The median thickness of voxels with thickness greater than 0 was defined as the thickness. This series of operations was carried out for five powder particles, and the average value was taken as the final powder surface thickness.

[0244] (Measurement 5) Open hole diameter of powder with particle diameter D50 The open pore diameter of the ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples was calculated according to the following procedure 5. [Step 5; Connecting hole diameter] 18.The thickness of S was calculated using BoneJ. 19. The median thickness of voxels with a thickness greater than 0 was taken as the diameter of the interconnected pores. This series of operations was carried out for five powder particles, and the average value was taken as the final interconnected pore diameter.

[0245] (Measurement 6) Ti and Al content in ultra-high molecular weight polyethylene powder The ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples were pressure-decomposed using a microwave decomposition apparatus (model ETHOS TC, manufactured by Milestone General Co., Ltd.), and the element concentrations of titanium (Ti) and aluminum (Al) as metals contained in the ultra-high molecular weight polyethylene powder were measured using an ICP-MS (inductively coupled plasma mass spectrometer, model X-series X7, manufactured by Thermo Fisher Scientific Co., Ltd.) by the internal standard method.

[0246] (Measurement 7) Average particle size (D50) of ultra-high molecular weight polyethylene powder The particle size of the ultra-high molecular weight polyethylene powder obtained in the examples and comparative examples was measured using a laser particle size distribution analyzer (SALD-2100 manufactured by Shimadzu Corporation). Measurements were performed using methanol as a dispersion medium, and a cumulative particle size distribution was created from the small particle size side based on the measurements. The particle size at the cumulative 50% was taken as the average particle size D50. This operation was repeated five times, and the average value of the three points excluding the maximum and minimum values ​​was calculated, and the final D50 was calculated.

[0247] (Method 1-1 for producing molded body) Method for producing separator (microporous membrane) for secondary battery with high polymer concentration Using the ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples, secondary battery separators were produced as follows. When the total amount of the ultra-high molecular weight polyethylene powder and the liquid paraffin is 100 parts by mass, 45 parts by mass of the ultra-high molecular weight polyethylene powder, 55 parts by mass of liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation), and 1 part by mass of an antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Co., Ltd.) are mixed together, and the melting point (T m2 ) and stirred for 30 minutes at a temperature 35° C. lower than the initial temperature to prepare a slurry liquid. The obtained slurry liquid was put into a Labo Plastomill (body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd., and kneaded at a constant temperature of 200°C for 10 minutes with a screw rotation speed of 50 rpm, and then heat-pressed at 180°C / 1 MPa / 3 minutes, further heat-pressed at 180°C / 10 MPa / 2 minutes, and then cooled and pressed at 25°C / 10 MPa / 5 minutes to form a gel sheet. The thickness of the gel sheet was adjusted to 1.0 mm by using a metal frame with a thickness of 1.0 mm. This gel-like sheet was stretched 7x7 times at 115°C using a simultaneous biaxial stretching machine, and the stretched film was cut into approximately 30cm squares and fixed to a metal frame with an inner dimension of 25cm square. It was then immersed in hexane to extract and remove the liquid paraffin, and then dried for more than 24 hours. It was then heat-set at 134°C for 1 minute to obtain a secondary battery separator.

[0248] (Method 1-2 for producing molded body) Method for producing separator (microporous membrane) for secondary battery with high polymer concentration Using the ultra-high molecular weight polyethylene powders obtained in the Examples and Comparative Examples, secondary battery separators were produced as follows. When the total amount of the ultra-high molecular weight polyethylene powder and the liquid paraffin is 100 parts by mass, 55 parts by mass of the ultra-high molecular weight polyethylene powder, 45 parts by mass of liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation), and 1 part by mass of an antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Co., Ltd.) are mixed together, and the melting point (T m2 ) and stirred for 60 minutes at a temperature 35°C lower than the initial temperature to prepare a slurry liquid. Next, the slurry liquid was poured into liquid paraffin (liquid paraffin manufactured by MORESCO Corporation (product name: Sumoil P-350P)) at 180° C. and stirred for 2 minutes to produce a gel with a polymer concentration of 45 parts by mass. The obtained slurry liquid was put into a Labo Plastomill (body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd., and kneaded at a constant temperature of 200°C for 10 minutes with a screw rotation speed of 50 rpm, and then heat-pressed at 180°C / 1 MPa / 3 minutes, further heat-pressed at 180°C / 10 MPa / 2 minutes, and then cooled and pressed at 25°C / 10 MPa / 5 minutes to form a gel sheet. The thickness of the gel sheet was adjusted to 1.0 mm by using a metal frame with a thickness of 1.0 mm. The gel-like sheet was stretched at 115°C by a simultaneous biaxial stretching machine in the range of 7x7 to 20x20 times to the limit at which the film ruptures, and then the stretched film was cut into approximately 30 cm square pieces and fixed to a metal frame with an inner dimension of 25 cm square. The film was then immersed in hexane to extract and remove the liquid paraffin, and then dried for 24 hours or more. It was then heat-set at 134°C for 1 minute to obtain a secondary battery separator.

[0249] (Method 2-1 for producing molded body) Method for producing separator for secondary battery with general polymer concentration A secondary battery separator was obtained in the same manner as described above (Method 1-1 for manufacturing molded body), except that, when the total amount of the ultra-high molecular weight polyethylene powder and liquid paraffin was 100 parts by mass, 25 parts by mass of the ultra-high molecular weight polyethylene powder, 75 parts by mass of liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation), and 1 part by mass of an antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxyhydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Co., Ltd.) were blended.

[0250] (Method 2-2 for producing molded body) Method for producing separator for secondary battery with general polymer concentration When the total amount of the ultra-high molecular weight polyethylene powder and liquid paraffin was 100 parts by mass, 35 parts by mass of the ultra-high molecular weight polyethylene powder, 65 parts by mass of liquid paraffin (liquid paraffin manufactured by MORESCO Corporation (product name: Sumoil P-350P)), and 1 part by mass of an antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Co., Ltd.) were blended, and the slurry liquid was then poured into liquid paraffin (liquid paraffin manufactured by MORESCO Corporation (product name: Sumoil P-350P)) at 180°C and stirred for 2 minutes to produce a gel with a polymer concentration of 25 parts by mass. Except for this, a separator for a secondary battery was obtained in the same manner as described above (Production method 1-2 of a molded body).

[0251] (Evaluation method 1) Number of defects in secondary battery separators A separator for a secondary battery is produced by the method described in the above (Production method 1-1 of a molded body), (Production method 1-2 of a molded body), (Production method 2-1 of a molded body) or (Production method 2-2 of a molded body), and 1 m of the obtained microporous membrane is 2The number of defects of 50 μm or more present in each microporous membrane (16 sheets of microporous membrane, 25 cm square) was counted visually, or using a magnifying glass if necessary. The term "defects" used here refers to areas that are darker in color than normal areas when the microporous membrane is observed with transmitted light (poor dispersion), and fibers and colored foreign matter are not counted as defects. Based on the number of defects found, the number of defects, which is one of the indicators of the quality of the microporous membrane, was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) ◎:15 pieces / m 2 less than ○:15 pieces / m 2 More than 45 pieces / m 2 less than △:45 pieces / m 2 More than 90 pieces / m 2 less than ×:90 pieces / m 2 End

[0252] (Evaluation method 2) Thickness variation of secondary battery separator A microporous membrane, which is a separator for a secondary battery, was produced by the method described in (Production method 1-1 for a molded body), (Production method 1-2 for a molded body), (Production method 2-1 for a molded body) or (Production method 2-2 for a molded body) above, and the thickness of the resulting microporous membrane was measured using a film thickness meter based on JIS K7130. For the measurement points, one 25 cm square microporous membrane was cut into 25 5 cm square microporous membranes, and the center of each was measured to calculate the average membrane thickness. Using the average membrane thickness as a standard, the thickness variation (hereinafter also referred to as membrane thickness unevenness), which is one of the indicators of the quality of the microporous membrane, was evaluated based on the following evaluation criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) ⊚: The film thickness varies by less than ±1.5 μm from the average film thickness. ◯: The film thickness varies by ±1.5 μm or more and less than ±2.0 μm from the average film thickness. △: The film thickness varies from the average film thickness by ±2.0 μm or more and less than ±4.0 μm. ×: The film thickness varies by ±4.0 μm or more from the average film thickness.

[0253] (Evaluation method 3) Puncture strength converted into basis weight (gf / (g / m 2)) Using a handy compression tester "KES-G5" manufactured by Kato Tech Co., Ltd., a microporous membrane that is a separator for a secondary battery described in (Production method 1-1 for molded body), (Production method 1-2 for molded body), (Production method 2-1 for molded body) or (Production method 2-2 for molded body) was fixed with a sample holder with an opening diameter of 10 mm. Next, a puncture test was performed on the center of the fixed microporous membrane with a needle tip curvature radius of 0.5 mm and a puncture speed of 10 mm / min to obtain the puncture strength (gf) as the maximum puncture load. The obtained puncture strength (gf) was divided by the basis weight to obtain the basis weight converted puncture strength (gf / (g / m 2 This operation was carried out eight times for eight microporous membranes, and the average of the eight measurements was calculated as the basis weight converted puncture strength (gf / (g / m 2 The evaluation results are shown in Table 1. (Evaluation Criteria) ☆: Puncture strength converted to unit weight is 95gf / (g / m 2 )That's all. ◎: The puncture strength converted into basis weight is 80gf / (g / m 2 ) or more 95gf / (g / m 2 ) or less. ○: The puncture strength converted to basis weight is 70gf / (g / m 2 ) or more 80gf / (g / m 2 ) or less. △: The puncture strength converted to unit weight is 60gf / (g / m 2 ) or more 70gf / (g / m 2 ) or less. ×: The puncture strength converted to basis weight is 60gf / (g / m 2 ) or less.

[0254] (Evaluation method 4) Heat shrinkage rate of secondary battery separator When producing the microporous membrane for secondary battery separator described in the above (Production method 1-1 for molded body), (Production method 1-2 for molded body), (Production method 2-1 for molded body) or (Production method 2-2 for molded body), the heat setting was performed under four conditions of 130°C / 1 minute, 132°C / 1 minute, 134°C / 1 minute, and 136°C / 1 minute, and the porosity of the obtained membrane after heat setting was calculated. The porosity was calculated by cutting a 10 cm x 10 cm square sample from the microporous membrane and measuring its volume (cm3 ) and mass (g), and compare them with the density of polyethylene (g / cm 3 ) was calculated using the following formula: Porosity (%) = (volume-mass / density) / volume x 100 In addition, the obtained heat-set membranes were sandwiched between sheets of paper, the stack of papers was placed in an envelope, and heated at 120°C for 1 hour. Then, it was cooled at room temperature for 15 minutes. The length of each side of the membrane was measured with a curved ruler, the average value was obtained, and the shrinkage rate from the original length (10 cm) was calculated to calculate the heat shrinkage rate. Here, a graph of porosity and heat shrinkage rate was created, and the heat shrinkage rate at a porosity of 50% was roughly calculated from the graph, and the superiority or inferiority of the membrane properties was evaluated based on the obtained heat shrinkage rate according to the following criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) ☆: Less than 10% ◎: 10% or more but less than 20% ○: 20% or more but less than 25% △: 25% to less than 30% ×: 30% or more

[0255] (Method 3-1 for manufacturing molded products) Method for manufacturing high-strength fibers using general kneading time A high-strength fiber was produced using ultra-high molecular weight polyethylene powder as follows. When the total amount of the ultra-high molecular weight polyethylene powder and liquid paraffin was 100 parts by mass, 15 parts by mass of the ultra-high molecular weight polyethylene powder, 85 parts by mass of liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation), and 1 part by mass of an antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Co., Ltd.) were blended to obtain a fiber having a melting point (T m2 ) and stirred for 60 minutes at a temperature 35°C lower than the initial temperature to prepare a slurry liquid. Next, the slurry liquid was poured into liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation) at 160°C and stirred for 2 minutes to produce a gel with a polymer concentration of 5 parts by mass. The resulting gel was poured into a Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. and kneaded at a constant temperature of 150°C for 180 minutes with a screw rotation speed of 10 rpm to produce a kneaded gel. Next, spinning was performed using a Capillograph 1D (main model: PMD-C) manufactured by Toyo Seiki Co., Ltd. The orifice had a hole diameter of 1.0 mm, a length of 66 mm, and an inlet angle of 90°. The kneaded gel was put into a furnace set at 180°C, and degassing was performed for 60 minutes. Thereafter, the extrusion speed was set to 7.5 mm / min so that the discharge amount was 0.35 g / min, and the raw yarn was collected at a winding speed of 2.8 m / min through a water bath directly below the tip of the orifice. The distance from the tip of the orifice to the surface of the water bath was 8 cm, and the temperature of the water bath was set to 20°C. After that, in order to remove the liquid paraffin from the wound raw yarn, it was immersed in hexane for extraction, and then dried for 24 hours. The raw yarn thus obtained was first drawn at a speed of 20 mm / min in a thermostatic bath at 120°C, and then secondarily drawn at a speed of 10 mm / min in a thermostatic bath at 140°C until the yarn broke, to obtain a high-strength fiber (drawn yarn). The temperature in the thermostatic bath was measured at the center of the bath with a thermometer.

[0256] (Method 3-2 for manufacturing molded products) Method for manufacturing high-strength fibers using normal mixing time A high-strength fiber was produced using ultra-high molecular weight polyethylene powder as follows. When the total amount of the ultra-high molecular weight polyethylene powder and liquid paraffin was 100 parts by mass, 15 parts by mass of the ultra-high molecular weight polyethylene powder, 85 parts by mass of liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation), and 1 part by mass of an antioxidant (tetrakis[methylene(3,5-di-t-butyl-4-hydroxy-hydrocinnamate)]methane (product name: ANOX20) manufactured by Great Lakes Chemical Japan Co., Ltd.) were blended to obtain a fiber having a melting point (Tm2 ) and stirred for 60 minutes at a temperature 35°C lower than the initial temperature to prepare a slurry liquid. Next, the slurry liquid was poured into liquid paraffin (liquid paraffin (product name: Sumoil P-350P) manufactured by MORESCO Corporation) at 180°C and stirred for 2 minutes to produce a gel with a polymer concentration of 5 parts by mass. The resulting gel was poured into a Labo Plastomill (main unit model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. and kneaded at a constant temperature of 150°C for 180 minutes with a screw rotation speed of 10 rpm to produce a kneaded gel. Next, spinning was performed using a Capilograph 1D (main model: PMD-C) manufactured by Toyo Seiki Co., Ltd. The orifice had a hole diameter of 1.0 mm, a length of 66 mm, and an inlet angle of 90°. The kneaded gel was put into a furnace set at 180°C, and degassing was performed for 60 minutes. Thereafter, the extrusion speed was set to 10 mm / min so that the discharge amount was 0.45 g / min, and the raw yarn was collected at a winding speed of 0.8 m / min through a water bath directly below the tip of the orifice. The distance from the tip of the orifice to the surface of the water bath was 8 cm, and the temperature of the water bath was set to 20°C. After that, in order to remove the liquid paraffin from the wound raw yarn, it was immersed in hexane for extraction, and then dried for 24 hours. The raw yarn thus obtained was first drawn in a thermostatic bath at 120°C with a delivery speed of 100mm / min and a winding speed of 3000mm / min, and then secondly drawn in a thermostatic bath at 140°C with a delivery speed of 100mm / min and a winding speed just before the yarn breaks, to obtain a high-strength fiber (drawn yarn). The drawing process was carried out using a heating and drawing device (main body type: IMC-3F08) manufactured by Imoto Manufacturing Co., Ltd. The temperature in the thermostatic bath was measured at the center of the bath using a thermometer.

[0257] (Method 4-1 for producing molded bodies) A ​​method for producing high-strength fibers in a short kneading time A high-strength fiber was obtained in the same manner as in the above (Production method 3-1 of molded body) except that the kneading time in a Labo Plastomill (main unit model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. was 60 minutes.

[0258] (Method 4-2 for manufacturing molded products) A method for manufacturing high-strength fibers in a short kneading time High-strength fibers were obtained in the same manner as described above (Method 3-2 for manufacturing molded bodies), except that the kneading time in a Labo Plastomill (main body model: 4C150-01) manufactured by Toyo Seiki Co., Ltd. was set to 0 minutes (no kneading in the Labo Plastomill).

[0259] (Evaluation method 5) Number of clumps of high-strength fibers The number of lumps of yarn generated in 10 m of high-strength fiber (drawn yarn) spun by the method described above in (Production method 3-1 for molded body), (Production method 3-2 for molded body), (Production method 4-1 for molded body) or (Production method 4-2 for molded body) was counted and the number of lumps of yarn was calculated. "Lumps of yarn" here refers to parts that are locally thicker than normal parts (poor dispersion). Based on the calculated number of lumps of yarn, the quality of the high-strength fiber was evaluated as follows. The evaluation results are shown in Table 1. (Evaluation Criteria) ◎: Number of thread clumps is less than 3 / m ○: Number of thread clumps is 3 or more and less than 6 / m △: Number of thread clumps is 6 or more and less than 10 / m ×: Number of clumps is 10 or more per meter

[0260] (Evaluation method 6) Unevenness in yarn diameter of high-strength fibers The diameter of 10 m of high strength fiber (drawn yarn) spun by the method described above in (Production method 3-1), (Production method 3-2), (Production method 4-1) or (Production method 4-2) was measured at 0.5 m intervals using an optical microscope, and the average yarn diameter was calculated. Using this average yarn diameter as a standard, the unevenness of the yarn diameter, which is one of the qualities of high strength fiber, was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) ◎: The variation from the average fiber diameter is less than ±3 μm. ◯: The variation is between ±3 μm and ±5 μm from the average fiber diameter. △: There is a variation of ±5 μm or more and less than ±10 μm from the average yarn diameter. ×: The average fiber diameter varies by ±10 μm or more.

[0261] (Evaluation method 7) Tensile breaking strength of high-strength fibers 10 m of high-strength fiber (drawn yarn) spun by the method described above in (Production method 3-1 for molded body), (Production method 3-2 for molded body), (Production method 4-1 for molded body) or (Production method 4-2 for molded body) was cut at 1 m intervals, and 10 of the obtained fibers were pulled until they broke under room temperature conditions, and the average breaking strength was calculated. At that time, the breaking strength was calculated by dividing the maximum load value applied to the yarn by the fineness. Here, the fineness means the 1×10 4 The weight (g) per meter was calculated from the weight of 10 meters of high strength fiber. The unit of fineness is dtex. The weight was measured using a balance capable of measuring to the nearest 0.1 mg. The evaluation results are shown in Table 1. The tensile breaking strength of the high strength fiber was evaluated according to the following criteria. (Evaluation Criteria) ☆: Breaking strength 43cN / dtex or more ◎: Breaking strength 30cN / dtex or more, less than 43cN / dtex ○: Breaking strength 25cN / dtex or more, less than 30cN / dtex △: Breaking strength 20cN / dtex or more, less than 25cN / dtex ×: Breaking strength less than 20 cN / dtex

[0262] (Evaluation method 8) Evaluation of high-speed winding properties of high-strength fibers The gel kneaded by the method described in (Production method 3-1), (Production method 3-2), (Production method 4-1) or (Production method 4-2) above was spun using a Capillograph 1D (body type: PMD-C) manufactured by Toyo Seiki Co., Ltd. The orifice used had a hole diameter of 0.5 mm, a length of 5 mm and an inlet angle of 90°. The spinning conditions were fixed at a temperature of 200°C and an extrusion speed of 20 mm / min, and the winding speed was increased from 3 m / min to 19.7 m / min. 2 The winding speed was gradually increased until the film broke, and the average of five measurements was used to evaluate the film according to the following criteria. The evaluation results are shown in Table 1. (Evaluation Criteria) ☆: High-speed winding speed is 900 m / min or more. ⊚: The high-speed winding speed is 700 m / min or more and less than 900 m / min. ◯: The high-speed winding speed is 400 m / min or more and less than 700 m / min. △: The high-speed winding speed is 200 m / min or more and less than 400 m / min. ×: The high-speed winding speed is less than 200 m / min.

[0263] (Measurement 8) Melting point (T m2 ) The melting points (T m2 ) was measured using a Perkin Elmer DSC8000 differential scanning calorimeter (DSC) as follows. 8.3-8.5 mg of polyethylene polymer powder was weighed out and placed in an aluminum sample pan. An aluminum cover was attached to this pan and placed in a differential scanning calorimeter. Measurements were performed under the following conditions while purging with nitrogen at a flow rate of 20 mL / min. Pure indium was used for temperature calibration. 1) After holding at 50°C for 1 minute, the temperature was increased to 180°C at a rate of 10°C / min. 2) After holding at 180°C for 5 minutes, the temperature was lowered to 50°C at a rate of 10°C / min. 3) After holding at 50°C for 5 minutes, the temperature was increased to 180°C at a rate of 10°C / min. The temperature at the peak top of the melting curve obtained during the temperature rise process in the above step 3 is called the melting peak temperature (T m2 ) was decided.

[0264] [Catalyst synthesis method] [Catalyst Production Example 1] (Preparation of Supported Metallocene Catalyst Component [A]) (1) Synthesis of raw material [a-1] Average particle size is 8μm and surface area is 400m 2 Spherical silica with a particle size of 0.8 ml / g and an intraparticle pore volume of 0.8 ml / g was calcined at 500°C for 5 hours in a nitrogen atmosphere and dehydrated. The number of silanol groups was 1.4 mmol / g. In a nitrogen atmosphere, 40 g of this dehydrated silica was dispersed in 800 mL of hexane in a 1.8 L capacity autoclave to obtain a slurry. While the obtained slurry was kept at 20° C. under stirring, 100 mL of a hexane solution of triethylaluminum (concentration: 1 mol / L) was added dropwise over 1 hour, and then the mixture was stirred at the same temperature for 2 hours. Thereafter, the resulting reaction mixture was decanted to remove unreacted triethylaluminum in the supernatant, thus obtaining 800 mL of a hexane slurry of the silica component [a-1] treated with triethylaluminum. (2) Preparation of raw material [a-2] 200 mmol of [(Nt-butylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter referred to as "titanium complex") was dissolved in 1250 mL of Isopar E [a trade name for a hydrocarbon mixture manufactured by Exxon Chemical Company (USA)], 25 mL of a 1 mol / L hexane solution of commercially available butylethylmagnesium was added, and further hexane was added to adjust the titanium complex concentration to 0.1 mol / L, thereby obtaining titanium complex [a-2]. (3) Preparation of raw material [a-3] 5.7 g of bis(hydrogenated tallow alkyl)methylammonium-tris(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter referred to as "borate") was added and dissolved in 50 mL of toluene to obtain a 100 mmol / L toluene solution of borate. 5 mL of a 1 mol / L hexane solution of ethoxydiethylaluminum was added to this toluene solution of borate at room temperature, and further hexane was added so that the borate concentration in the solution became 70 mmol / L. After that, the mixture was stirred at room temperature for 1 hour to obtain a reaction mixture [a-3] containing borate. (4) Synthesis of supported metallocene catalyst [A] 800 mL of the silica component [a-1] slurry obtained in (1) above was stirred at 20°C, and 48 mL of the titanium complex [a-2] obtained in (2) above and 69 mL of the reaction mixture [a-3] containing borate obtained in (3) above were added simultaneously over 1 hour, and the mixture was stirred at the same temperature for another 1 hour to react the titanium complex with the borate. The catalytic activity can be controlled by adjusting the amounts of the titanium complex [a-2] and the reaction mixture [a-3] containing borate here. Specifically, the catalytic activity tends to increase by increasing the amounts of these. After the reaction was completed, the supernatant was removed, and the unreacted catalyst raw material was removed with hexane to obtain a supported metallocene catalyst [A] in which catalytically active species were formed on the silica (hereinafter also referred to as solid catalyst component [A] or solid catalyst A). (5) Synthesis of raw material (a-4) In a fully nitrogen-purged 8L stainless steel autoclave, 2,000mL of 1mol / L hexane solution of 6[Mg(C4H9)2]·Al(C2H5)3 (equivalent to 2000mmol of magnesium and aluminum) was charged, and while stirring at 80℃, 240mL of hexane solution of 8.33mol / L methylhydrogenpolysiloxane (Shin-Etsu Chemical Co., Ltd.) was pumped in, and stirring was continued for another 2 hours at 80℃. After the reaction was completed, the mixture was cooled to room temperature and used as raw material (a-4). The total concentration of magnesium and aluminum in raw material (a-4) was 0.786mol / L.

[0265] [Catalyst Production Example 2] (Preparation of solid catalyst component [B]) (1) Synthesis of raw material (b-1) 2,000mmol of 6[Mg(C4H9)2]·Al(C2H5)3 was charged into an 8L stainless steel autoclave that had been thoroughly purged with nitrogen, and after diluting with hexane, 800mmol of n-butanol in hexane was added dropwise over 3 hours while stirring at 50℃. After completion of the reaction, the line was washed with 300mL of hexane. Stirring was continued for another 2 hours at 50℃. After the reaction was completed, the mixture was cooled to room temperature and used as raw material [b-1]. (2) Synthesis of raw material [b-2] In a thoroughly nitrogen-purged 8L stainless steel autoclave, 2,000mL of 1mol / L hexane solution of 6[Mg(C4H9)2]·Al(C2H5)3 (equivalent to 2000mmol of magnesium and aluminum) was stirred at 80℃, while 240mL of hexane solution of 8.33mol / L methylhydrogenpolysiloxane (Shin-Etsu Chemical Co., Ltd.) was pumped in, and stirring was continued for another 2 hours at 80℃. After the reaction was completed, the mixture was cooled to room temperature and used as raw material [b-2]. The total concentration of magnesium and aluminum in raw material [b-2] was 0.786mol / L. (3) [B-1] Synthesis of carrier A 1,000mL hexane solution of 1mol / L trichlorosilane was placed in an 8L stainless steel autoclave that had been thoroughly purged with nitrogen, and a hexane solution of the raw material [b-1], an organomagnesium compound equivalent to 943mmol of magnesium, was added dropwise over 3 hours at 65°C, and the reaction was continued for another 1 hour at 65°C with stirring. After the reaction was completed, the supernatant was removed and the mixture was washed four times with 1,800mL of hexane to obtain the [B-1] carrier. Analysis of this carrier revealed that it contained 7.5mmol of magnesium per 1g of solid. (4) Preparation of solid catalyst component [B] To 1,970 mL of hexane slurry containing 110 g of the above-mentioned [B-1] carrier, 103 mL of a 1 mol / L hexane solution of titanium tetrachloride and 131 mL of the raw material [b-2] were added simultaneously over a period of 3 hours while stirring at 10°C. After the addition, the reaction was continued for 1 hour at 10°C. After the reaction was completed, the supernatant was removed and the unreacted raw material components were removed by washing four times with hexane, to prepare the solid catalyst component [B].

[0266] [Catalyst Production Example 3] (Preparation of solid catalyst component [C]) (1) Synthesis of raw material (c-1) In a fully nitrogen-purged 8L stainless steel autoclave, 2,000mL of 1mol / L hexane solution of 6[Mg(C4H9)2]·Al(C2H5)3 (equivalent to 2,000mmol of magnesium and aluminum) was charged, and 240mL of hexane solution of 8.33mol / L methylhydrogenpolysiloxane (Shin-Etsu Chemical Co., Ltd.) was pumped in while stirring at 80℃, and the reaction was continued for another 2 hours at 80℃ while stirring. After the reaction was completed, the mixture was cooled to room temperature and used as raw material (c-1). The total concentration of magnesium and aluminum in raw material (c-1) was 0.786mol / L. (2) Preparation of solid catalyst component [C] 1,600 mL of hexane was added to an 8 L stainless steel autoclave purged with nitrogen. While stirring at 10°C, 800 mL of a 1 mol / L hexane solution of titanium tetrachloride and 800 mL of raw material (c-1) were added simultaneously over 5 hours. The reaction was continued at 10°C for 1 hour. After the reaction was completed, the supernatant was removed and the unreacted raw material components were removed by washing with hexane four times to prepare a solid catalyst component [C] (hereinafter also referred to as solid catalyst C). The catalytic activity of this catalyst can be adjusted by the polymerization pressure during polymerization.

[0267] [Co-catalyst] As the cocatalysts, the following cocatalysts 1 to 3 were used. Cocatalyst 1: A mixture of commercially available triisobutylaluminum and diisobutylaluminum hydride (a 9:1 mixture by mass). Cocatalyst 2:6[Mg(C4H9)2]·Al(C2H5)3 Co-catalyst 3: the above-synthesized raw material (a-4), raw material (b-2), or raw material (c-1)

[0268] [Example 1] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Next, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.045MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.1MPa. Then, 5.0mg of solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a stainless steel beaker with a diameter of 68 mm, and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50°C under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 18,000 (g-PE / g-catalyst). Scale and extremely coarse powder were removed using a sieve with 425 μm openings, and 600 ppm of calcium stearate was added, after which the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Molded body production method 1-1), (Molded body production method 1-2), (Molded body production method 2-1) and (Molded body production method 2-2), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1.

[0269] [Example 2] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 20°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 15NL with a flow meter, 750.0mg of solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 2) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 2 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.045MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst 2 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50°C under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 24,000 (g-PE / g-catalyst). Scale and extremely coarse powder were removed using a sieve with 425 μm openings, and after adding 600 ppm of calcium stearate, the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Molded body production method 1-1), (Molded body production method 1-2), (Molded body production method 2-1) and (Molded body production method 2-2), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1.

[0270] [Example 3] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 20°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 15NL with a flow meter, 750.0mg of solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 3) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 3 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.016MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst 3 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50°C under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 26,500 (g-PE / g-catalyst). Scale and extremely coarse powder were removed using a sieve with 425 μm openings, and after adding 600 ppm of calcium stearate, the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Molded body production method 1-1), (Molded body production method 1-2), (Molded body production method 2-1) and (Molded body production method 2-2), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1.

[0271] [Example 4] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 15°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 15NL with a flow meter, 750.0mg of solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 4) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 4 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.0036MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst 4 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 60°C under vacuum for 4 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 26,000 (g-PE / g-catalyst). Scale and extremely coarse powder were removed using a sieve with 425 μm openings, and after adding 600 ppm of calcium stearate, the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Molded body production method 1-1), (Molded body production method 1-2), (Molded body production method 2-1) and (Molded body production method 2-2), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1.

[0272] [Example 5] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of a mixed solvent in which 45% by mass of dehydrated normal hexane and 55% by mass of liquid paraffin were thoroughly mixed in advance was introduced into the polymerization reactor. Then, 5.0mL of the cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 15°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 15NL with a flow meter, 750.0mg of the solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 5) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 5 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.0036MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst 5 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain an ultra-high molecular weight polyethylene powder. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 24,200 (g-PE / g-catalyst). Scale and extremely coarse powder were removed using a sieve with 425 μm openings, and after adding 600 ppm of calcium stearate, the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Molded body production method 1-1), (Molded body production method 1-2), (Molded body production method 2-1) and (Molded body production method 2-2), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1.

[0273] [Example 6] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of cocatalyst 2 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 10°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 10NL with a flow meter, 750.0mg of solid catalyst component [B] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 6) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 6 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500 mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6 mL of cocatalyst 2 was dispersed in 100 mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 78 ° C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) was introduced so that the pressure in the polymerization reactor was 0.00035 MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8 MPa. Then, 40.0 mg of prepolymerization catalyst 6 was dispersed in 200 mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately additionally introducing ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 60°C under vacuum for 4 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 21,350 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1), (Production method 3-2), (Production method 4-1) and (Production method 4-2), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0274] [Example 7] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirrer, 500mL of a mixed solvent prepared by thoroughly mixing 35% by mass of dehydrated normal hexane and 65% by mass of liquid paraffin was introduced into the polymerization reactor. Then, 5.0mL of the cocatalyst 2 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 10°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 10NL with a flow meter, 750.0mg of the solid catalyst component [B] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 7) ​​was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 7 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500 mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6 mL of cocatalyst 2 was dispersed in 100 mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 78 ° C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen for adjusting the intrinsic viscosity IV (molecular weight) was introduced so that the pressure in the polymerization reactor was 0.00035 MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.7 MPa. Then, 40.0 mg of prepolymerization catalyst 7 was dispersed in 200 mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately additionally introducing ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain an ultra-high molecular weight polyethylene powder. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 21,000 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1), (Production method 3-2), (Production method 4-1) and (Production method 4-2), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0275] [Example 8] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of cocatalyst 2 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 10°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 10NL with a flow meter, 750.0mg of solid catalyst component [B] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 8) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 8 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 2 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 58°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.7MPa. Then, 40.0mg of prepolymerized catalyst 8 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid component. The obtained solid component was placed in a stainless steel beaker with a diameter of 68mm, and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 70°C under vacuum for 4 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 19,000 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1), (Production method 3-2), (Production method 4-1) and (Production method 4-2), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0276] [Example 9] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of the cocatalyst 3 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 8°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 5NL with a flow meter, 750.0mg of the solid catalyst component [A] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 9) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 9 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 3 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 70°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst 9 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid component. The obtained solid component was placed in a stainless steel beaker with a diameter of 68mm, and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 80°C under vacuum for 6 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 28,000 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1), (Production method 3-2), (Production method 4-1) and (Production method 4-2), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0277] [Example 10] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of the cocatalyst 3 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 5°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 5NL with a flow meter, 750.0mg of the solid catalyst component [A] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst 10) was extracted into a nitrogen glove and collected. Next, the collected prepolymerized catalyst 10 was used to carry out main polymerization. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 3 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 60°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst 10 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid component. The obtained solid component was placed in a stainless steel beaker with a diameter of 68mm, and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 90°C under vacuum for 6 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 26,000 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1), (Production method 3-2), (Production method 4-1) and (Production method 4-2), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0278] [Comparative Example 1] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 20°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 15NL with a flow meter, 750.0mg of solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst H-1) was extracted into a nitrogen glove and collected. Next, main polymerization was carried out using the collected prepolymerization catalyst H-1. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Then, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.05MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst H-1 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 50°C under vacuum for 3 hours, then immersed in hexane for 10 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 24,500 (g-PE / g-catalyst). Scale and extremely coarse powder were removed using a sieve with 425 μm openings, and after adding 600 ppm of calcium stearate, the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Production method of molded body 1-1) and (Production method of molded body 2-1), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1. [Comparative Example 2] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 5.0mL of the cocatalyst 3 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 5°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene was adjusted to 5NL with a flow meter, 750.0mg of the solid catalyst component [A] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch-type prepolymerization reaction was carried out for 1.0 hour. After the reaction was completed, the obtained prepolymerization catalyst (hereinafter also referred to as prepolymerization catalyst H-2) was extracted into a nitrogen glove and collected. Next, main polymerization was carried out using the collected prepolymerization catalyst H-2. After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 3 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 58°C, and stirring was started at a rotation speed of 1,000 rpm. Then, ethylene gas was introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 40.0mg of prepolymerization catalyst H-2 was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid components were placed in a stainless steel beaker with a diameter of 68mm, and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain ultra-high molecular weight polyethylene powder. Next, the ultra-high molecular weight polyethylene powder was immersed in liquid paraffin adjusted to 90°C under vacuum for 6 hours, then immersed in hexane for 15 hours to extract the liquid paraffin, and dried at 25°C for 24 hours. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 22,500 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1 for molded body) and (Production method 4-1 for molded body), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0279] [Comparative Example 3] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 1 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 80°C, and stirring was started at a rotation speed of 1,000 rpm. Next, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.016MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.8MPa. Then, 5.0mg of solid catalyst component [C] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a 68 mm diameter stainless steel beaker and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm to obtain ultra-high molecular weight polyethylene powder. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 27,000 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and 600 ppm of calcium stearate was added, after which the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce microporous membranes for secondary battery separators by the methods described above in (Production method of molded body 1-1) and (Production method of molded body 2-1), and evaluated by the above evaluation methods 1 to 4. The evaluation results of the obtained microporous membranes are shown in Table 1.

[0280] [Comparative Example 4] After evacuating the inside of a vessel-type 1.5L polymerization reactor equipped with a stirring device, 500mL of dehydrated normal hexane was introduced into the polymerization reactor. Then, 0.6mL of cocatalyst 2 was dispersed in 100mL of dehydrated normal hexane and introduced into the polymerization reactor, the temperature of the polymerization reactor was adjusted to 78°C, and stirring was started at a rotation speed of 1,000 rpm. Next, hydrogen was introduced to adjust the intrinsic viscosity IV (molecular weight) so that the pressure in the polymerization reactor was 0.00035MPa, and ethylene was further introduced so that the pressure in the polymerization reactor was 0.7MPa. Then, 5.0mg of solid catalyst component [B] was dispersed in 200mL of dehydrated normal hexane and introduced into the polymerization reactor, and a batch polymerization reaction was carried out for 1.0 hour. During the polymerization reaction, the pressure in the polymerization reactor was maintained by appropriately introducing additional ethylene into the polymerization reactor. Then, the polymerization reactor was opened, and the contents were filtered under reduced pressure to separate and recover the powder-like solid components. The obtained solid component was placed in a stainless steel beaker with a diameter of 68 mm and dried at 70°C for 2 hours while stirring at a stirring speed of 50 rpm, yielding ultra-high molecular weight polyethylene powder. The catalytic activity of the ultra-high molecular weight polyethylene powder (amount of polyethylene obtained per unit catalyst weight) was 23,500 (g-PE / g-catalyst). Scale and extremely coarse particles were removed using a sieve with 425 μm openings, and the physical properties of the ultra-high molecular weight polyethylene powder were evaluated. The evaluation results of the ultra-high molecular weight polyethylene powder are shown in Table 1. The obtained ultra-high molecular weight polyethylene powder was used to produce high strength fibers by the methods described above in (Production method 3-1 for molded body) and (Production method 4-1 for molded body), and the fibers were evaluated by the above evaluation methods 5 to 8. The evaluation results of the obtained high strength fibers are shown in Table 1.

[0281] [Table 1-1] [Table 1-2] [Table 1-3] [Industrial Applicability]

[0282] INDUSTRIAL APPLICABILITY The ultra-high molecular weight polyethylene powder of the present invention has excellent moldability and can provide high-quality molded articles, such as separators and fibers for secondary batteries, by shortening the dissolution time in liquid paraffin (the time from the start of dissolution to the end of dissolution), and has industrial applicability.

Claims

1. The intrinsic viscosity IV is 1.0 dL / g or more and 38.0 dL / g or less, The average particle diameter D50 is 50 μm or more and 400 μm or less, The dissolution time of a powder having a particle size of D50 is 5 seconds or more and 80 seconds or less. Ultra-high molecular weight polyethylene powder.

2. The intrinsic viscosity IV is 13.5 dL / g or more and 38.0 dL / g or less; The ultra-high molecular weight polyethylene powder according to claim 1.

3. The dissolution time is 5 seconds or more and 40 seconds or less. The ultra-high molecular weight polyethylene powder according to claim 1 or 2.

4. The ratio of open pores in the powder having a particle diameter of D50 is 3% or more and 70% or less. The ultra-high molecular weight polyethylene powder according to claim 1 or 2.

5. The surface thickness of a powder having a particle diameter of D50 is 3 μm or more and 60 μm or less. The ultra-high molecular weight polyethylene powder according to claim 1 or 2.

6. The diameter of the continuous hole of the powder having a particle diameter of D50 is 3 μm or more and 30 μm or less. The ultra-high molecular weight polyethylene powder according to claim 1 or 2.

7. The titanium content is 5 ppm or less. The ultra-high molecular weight polyethylene powder according to claim 1 or 2.

8. The aluminum content is 5 ppm or less. The ultra-high molecular weight polyethylene powder according to claim 1 or 2.

9. A molded article of the ultra-high molecular weight polyethylene powder according to claim 1 or 2.

10. The molded article is a separator for a secondary battery. The molded article according to claim 9.

11. The molded body is a fiber. The molded article according to claim 9.

12. a slurry process of mixing the ultra-high molecular weight polyethylene powder with a first liquid paraffin and stirring the mixture at a temperature equal to or lower than the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry; a gelling step of mixing the slurry with a second liquid paraffin having a temperature of 150° C. or more and 300° C. or less to obtain a gel for raw yarn having a temperature of 140° C. or more and 200° C. or less; an extrusion step of extruding the gel to obtain a raw yarn; an extraction step of extracting the first liquid paraffin and the second liquid paraffin from the raw yarn to obtain a raw yarn for drawing; a yarn drawing step of heating and drawing the yarn to be drawn; having The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 13.5 dL / g or more and 38.0 dL / g or less, The ultra-high molecular weight polyethylene powder has an average particle diameter D50 of 50 μm or more and 400 μm or less, The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds or more and 80 seconds or less. A method for producing high strength fibers.

13. The method for producing a high-strength fiber according to claim 12, further comprising a kneading step of kneading the yarn gel prior to the extrusion step.

14. a slurry process of mixing the ultra-high molecular weight polyethylene powder with a first liquid paraffin and stirring the mixture at a temperature equal to or lower than the melting point of the ultra-high molecular weight polyethylene powder to obtain a slurry; A gelling step of mixing the slurry with a second liquid paraffin having a temperature of 150° C. or more and 300° C. or less to obtain a gel for pressing having a temperature of 140° C. or more and 200° C. or less; a pressing step of hot pressing the gel for pressing to obtain a gel sheet; A film stretching step of stretching the gel sheet to obtain a stretched film; an extraction step of extracting the first liquid paraffin and the second liquid paraffin from the stretched membrane; having The ultra-high molecular weight polyethylene powder has an intrinsic viscosity IV of 1.0 dL / g or more and 13.0 dL / g or less, The ultra-high molecular weight polyethylene powder has an average particle diameter D50 of 50 μm or more and 400 μm or less, The dissolution time of the powder having a particle size of D50 of the ultra-high molecular weight polyethylene powder is 5 seconds or more and 80 seconds or less. A method for producing a microporous membrane.

15. The method for producing a microporous membrane according to claim 14, further comprising a kneading step of kneading the pressing gel prior to the pressing step.

Citation Information

Patent Citations

  • Polyethylene powder and fiber

    JP2017088773A

  • Polyethylene-based powder and manufacturing method thereof

    JP2017145306A

  • Polyethylen powder

    JP2019019265A

  • Polyethylenic polymer powder and lithium ion secondary battery separator

    JP2019070117A

  • Ethylene polymer and molded body using the same

    JP2019123777A